Early queen infection shapes developmental dynamics and induces long-term disease protection in incipient ant colonies - Casillas Perez, Barbara E; Pull, Christopher; Naiser, Filip; Naderlinger, Elisabeth; Matas, Jiri; Cremer, Sylvia
Infections early in life can have enduring effects on an organism’s development and immunity. In this study, we show that this equally applies to developing “superorganisms” – incipient social insect colonies. When we exposed newly mated Lasius niger ant queens to a low pathogen dose, their colonies grew more slowly than controls before winter, but reached similar sizes afterwards. Independent of exposure, queen hibernation survival improved when the ratio of pupae to workers was small. Queens that reared fewer pupae before worker emergence exhibited lower pathogen levels, indicating that high brood rearing efforts interfere with the ability of the queen’s immune system to suppress pathogen proliferation. Early-life queen pathogen-exposure also improved the immunocompetence of her worker offspring, as demonstrated by challenging the workers to the same pathogen a year later. Transgenerational transfer of the queen’s pathogen experience to her workforce can hence durably reduce the disease susceptibility of the whole superorganism.

Control of protein synthesis and memory by GluN3A-NMDA receptors through inhibition of GIT1/mTORC1 assembly - Conde-Dusman, María J; Dey, Partha N; Elía-Zudaire, Óscar; Garcia Rabaneda, Luis E; García-Lira, Carmen; Grand, Teddy; Briz, Victor; Velasco, Eric R; Andero Galí, Raül; Niñerola, Sergio; Barco, Angel; Paoletti, Pierre; et al. (eLife)
De novo protein synthesis is required for synapse modifications underlying stable memory encoding. Yet neurons are highly compartmentalized cells and how protein synthesis can be regulated at the synapse level is unknown. Here, we characterize neuronal signaling complexes formed by the postsynaptic scaffold GIT1, the mechanistic target of rapamycin (mTOR) kinase, and Raptor that couple synaptic stimuli to mTOR-dependent protein synthesis; and identify NMDA receptors containing GluN3A subunits as key negative regulators of GIT1 binding to mTOR. Disruption of GIT1/mTOR complexes by enhancing GluN3A expression or silencing GIT1 inhibits synaptic mTOR activation and restricts the mTOR-dependent translation of specific activity-regulated mRNAs. Conversely, GluN3A removal enables complex formation, potentiates mTOR-dependent protein synthesis, and facilitates the consolidation of associative and spatial memories in mice. The memory enhancement becomes evident with light or spaced training, can be achieved by selectively deleting GluN3A from excitatory neurons during adulthood, and does not compromise other aspects of cognition such as memory flexibility or extinction. Our findings provide mechanistic insight into synaptic translational control and reveal a potentially selective target for cognitive enhancement.
Keywords: general immunology and microbiology; general biochemistry; genetics and molecular biology; general medicine; general neuroscience

Towards best practices in research: Role of academic core facilities - Restivo, Leonardo; Gerlach, Björn; Tsoory, Michael; Bikovski, Lior; Badurek, Sylvia; Pitzer, Claudia; Kos-Braun, Isabelle C.; Mausset-Bonnefont, Anne Laure Mj; Ward, Jonathan; Schunn, Michael; Noldus, Lucas P.J.J.; Bespalov, Anton; et al. (EMBO Reports)
During the past decade, the scientific community and outside observers have noted a concerning lack of rigor and transparency in preclinical research that led to talk of a “reproducibility crisis” in the life sciences (Baker, 2016; Bespalov & Steckler, 2018; Heddleston et al, 2021). Various measures have been proposed to address the problem: from better training of scientists to more oversight to expanded publishing practices such as preregistration of studies. The recently published EQIPD (Enhancing Quality in Preclinical Data) System is, to date, the largest initiative that aims to establish a systematic approach for increasing the robustness and reliability of biomedical research (Bespalov et al, 2021). However, promoting a cultural change in research practices warrants a broad adoption of the Quality System and its underlying philosophy. It is here that academic Core Facilities (CF), research service providers at universities and research institutions, can make a difference. It is fair to assume that a significant fraction of published data originated from experiments that were designed, run, or analyzed in CFs. These academic services play an important role in the research ecosystem by offering access to cutting-edge equipment and by developing and testing novel techniques and methods that impact research in the academic and private sectors alike (Bikovski et al, 2020). Equipment and infrastructure are not the only value: CFs employ competent personnel with profound knowledge and practical experience of the specific field of interest: animal behavior, imaging, crystallography, genomics, and so on. Thus, CFs are optimally positioned to address concerns about the quality and robustness of preclinical research.

Cryo-EM structure of a functional monomeric Photosystem I from Thermosynechococcus elongatus reveals red chlorophyll cluster - Çoruh, Mehmet Orkun; Frank, Anna; Tanaka, Hideaki; Kawamoto, Akihiro; El-Mohsnawy, Eithar; Kato, Takayuki; Namba, Keiichi; Gerle, Christoph; Nowaczyk, Marc M.; Kurisu, Genji (Communications Biology)
A high-resolution structure of trimeric cyanobacterial Photosystem I (PSI) from Thermosynechococcus elongatus was reported as the first atomic model of PSI almost 20 years ago. However, the monomeric PSI structure has not yet been reported despite long-standing interest in its structure and extensive spectroscopic characterization of the loss of red chlorophylls upon monomerization. Here, we describe the structure of monomeric PSI from Thermosynechococcus elongatus BP-1. Comparison with the trimer structure gave detailed insights into monomerization-induced changes in both the central trimerization domain and the peripheral regions of the complex. Monomerization-induced loss of red chlorophylls is assigned to a cluster of chlorophylls adjacent to PsaX. Based on our findings, we propose a role of PsaX in the stabilization of red chlorophylls and that lipids of the surrounding membrane present a major source of thermal energy for uphill excitation energy transfer from red chlorophylls to P700.
Keywords: general agricultural and biological Sciences; general biochemistry; genetics and molecular biology; medicine (miscellaneous)

A coupled mechano-biochemical model for cell polarity guided anisotropic root growth - Marconi, Marco; Gallemi, Marçal; Benková, Eva; Wabnik, Krzysztof (eLife)
Plants develop new organs to adjust their bodies to dynamic changes in the environment. How independent organs achieve anisotropic shapes and polarities is poorly understood. To address this question, we constructed a mechano-biochemical model for Arabidopsis root meristem growth that integrates biologically plausible principles. Computer model simulations demonstrate how differential growth of neighboring tissues results in the initial symmetry-breaking leading to anisotropic root growth. Furthermore, the root growth feeds back on a polar transport network of the growth regulator auxin. Model, predictions are in close agreement with in vivo patterns of anisotropic growth, auxin distribution, and cell polarity, as well as several root phenotypes caused by chemical, mechanical, or genetic perturbations. Our study demonstrates that the combination of tissue mechanics and polar auxin transport organizes anisotropic root growth and cell polarities during organ outgrowth. Therefore, a mobile auxin signal transported through immobile cells drives polarity and growth mechanics to coordinate complex organ development.

Experimental observation of the origin and structure of elastoinertial turbulence - Choueiri, George H; Lopez Alonso, Jose M; Varshney, Atul; Sankar, Sarath; Hof, Björn (Proceedings of the National Academy of Sciences)
Turbulence generally arises in shear flows if velocities and hence, inertial forces are sufficiently large. In striking contrast, viscoelastic fluids can exhibit disordered motion even at vanishing inertia. Intermediate between these cases, a state of chaotic motion, “elastoinertial turbulence” (EIT), has been observed in a narrow Reynolds number interval. We here determine the origin of EIT in experiments and show that characteristic EIT structures can be detected across an unexpectedly wide range of parameters. Close to onset, a pattern of chevron-shaped streaks emerges in qualitative agreement with linear and weakly nonlinear theory. However, in experiments, the dynamics remain weakly chaotic, and the instability can be traced to far lower Reynolds numbers than permitted by theory. For increasing inertia, the flow undergoes a transformation to a wall mode composed of inclined near-wall streaks and shear layers. This mode persists to what is known as the “maximum drag reduction limit,” and overall EIT is found to dominate viscoelastic flows across more than three orders of magnitude in Reynolds number.
Keywords: multidisciplinary; elastoinertial turbulence; viscoelastic flows; elastic instability; drag reduction

Metamachines of pluripotent colloids - Aubret, Antoine; Martinet, Quentin; Palacci, Jérémie A (Nature Communications)
Machines enabled the Industrial Revolution and are central to modern technological progress: A machine’s parts transmit forces, motion, and energy to one another in a predetermined manner. Today’s engineering frontier, building artificial micromachines that emulate the biological machinery of living organisms, requires faithful assembly and energy consumption at the microscale. Here, we demonstrate the programmable assembly of active particles into autonomous metamachines using optical templates. Metamachines, or machines made of machines, are stable, mobile and autonomous architectures, whose dynamics stems from the geometry. We use the interplay between anisotropic force generation of the active colloids with the control of their orientation by local geometry. This allows autonomous reprogramming of active particles of the metamachines to achieve multiple functions. It permits the modular assembly of metamachines by fusion, reconfiguration of metamachines and, we anticipate, a shift in focus of self-assembly towards active matter and reprogrammable materials.

Neuronal HSF-1 coordinates the propagation of fat desaturation across tissues to enable adaptation to high temperatures in C. elegans - Chauve, Laetitia; Hodge, Francesca; Murdoch, Sharlene; Masoudzadeh, Fatemah; Mann, Harry Jack; Lopez-Clavijo, Andrea; Okkenhaug, Hanneke; West, Greg; Sousa, Bebiana C.; Segonds-Pichon, Anne; Li, Cheryl; Wingett, Steven; et al. (PLoS Biology)
To survive elevated temperatures, ectotherms adjust the fluidity of membranes by fine-tuning lipid desaturation levels in a process previously described to be cell autonomous. We have discovered that, in Caenorhabditis elegans, neuronal heat shock factor 1 (HSF-1), the conserved master regulator of the heat shock response (HSR), causes extensive fat remodeling in peripheral tissues. These changes include a decrease in fat desaturase and acid lipase expression in the intestine and a global shift in the saturation levels of plasma membrane’s phospholipids. The observed remodeling of plasma membrane is in line with ectothermic adaptive responses and gives worms a cumulative advantage to warm temperatures. We have determined that at least 6 TAX-2/TAX-4 cyclic guanosine monophosphate (cGMP) gated channel expressing sensory neurons, and transforming growth factor ß (TGF-β)/bone morphogenetic protein (BMP) are required for signaling across tissues to modulate fat desaturation. We also find neuronal hsf-1 is not only sufficient but also partially necessary to control the fat remodeling response and for survival at warm temperatures. This is the first study to show that a thermostat-based mechanism can cell nonautonomously coordinate membrane saturation and composition across tissues in a multicellular animal.

The beauty of random polytopes inscribed in the 2-sphere - Akopyan, Arseniy; Edelsbrunner, Herbert; Nikitenko, Anton (Experimental Mathematics)
Consider a random set of points on the unit sphere in ℝd, which can be either uniformly sampled or a Poisson point process. Its convex hull is a random inscribed polytope, whose boundary approximates the sphere. We focus on the case d = 3, for which there are elementary proofs and fascinating formulas for metric properties. In particular, we study the fraction of acute facets, the expected intrinsic volumes, the total edge length, and the distance to a fixed point. Finally we generalize the results to the ellipsoid with homeoid density.

How do chaperones bind (partly) unfolded client proteins? - Sučec, Iva; Bersch, Beate; Schanda, Paul (Frontiers in Molecular Biosciences)
Molecular chaperones are central to cellular protein homeostasis. Dynamic disorder is a key feature of the complexes of molecular chaperones and their client proteins, and it facilitates the client release towards a folded state or the handover to downstream components. The dynamic nature also implies that a given chaperone can interact with many different client proteins, based on physico-chemical sequence properties rather than on structural complementarity of their (folded) 3D structure. Yet, the balance between this promiscuity and some degree of client specificity is poorly understood. Here, we review recent atomic-level descriptions of chaperones with client proteins, including chaperones in complex with intrinsically disordered proteins, with membrane-protein precursors, or partially folded client proteins. We focus hereby on chaperone-client interactions that are independent of ATP. The picture emerging from these studies highlights the importance of dynamics in these complexes, whereby several interaction types, not only hydrophobic ones, contribute to the complex formation. We discuss these features of chaperone-client complexes and possible factors that may contribute to this balance of promiscuity and specificity.

Catabolism of strigolactones by a carboxylesterase - Xu, Enjun; Chai, Liang; Zhang, Shiqi; Yu, Ruixue; Zhang, Xixi; Xu, Chongyi; Hu, Yuxin (Nature Plants)
Strigolactones (SLs) are carotenoid-derived plant hormones that control shoot branching and communications between host plants and symbiotic fungi or root parasitic plants. Extensive studies have identified the key components participating in SL biosynthesis and signalling, whereas the catabolism or deactivation of endogenous SLs in planta remains largely unknown. Here, we report that the Arabidopsis carboxylesterase 15 (AtCXE15) and its orthologues function as efficient hydrolases of SLs. We show that overexpression of AtCXE15 promotes shoot branching by dampening SL-inhibited axillary bud outgrowth. We further demonstrate that AtCXE15 could bind and efficiently hydrolyse SLs both in vitro and in planta. We also provide evidence that AtCXE15 is capable of catalysing hydrolysis of diverse SL analogues and that such CXE15-dependent catabolism of SLs is evolutionarily conserved in seed plants. These results disclose a catalytic mechanism underlying homoeostatic regulation of SLs in plants, which also provides a rational approach to spatial-temporally manipulate the endogenous SLs and thus architecture of crops and ornamental plants.

Neuronal HSF-1 coordinates the propagation of fat desaturation across tissues to enable adaptation to high temperatures in C. elegans - Chauve, Laetitia; Hodge, Francesca; Murdoch, Sharlene; Masoudzadeh, Fatemah; Mann, Harry-Jack; Lopez-Clavijo, Andrea; Okkenhaug, Hanneke; West, Greg; Sousa, Bebiana C.; Segonds-Pichon, Anne; Li, Cheryl; Wingett, Steven; et al.
To survive elevated temperatures, ectotherms adjust the fluidity of membranes by fine-tuning lipid desaturation levels in a process previously described to be cell-autonomous. We have discovered that, in Caenorhabditis elegans, neuronal Heat shock Factor 1 (HSF-1), the conserved master regulator of the heat shock response (HSR)- causes extensive fat remodelling in peripheral tissues. These changes include a decrease in fat desaturase and acid lipase expression in the intestine, and a global shift in the saturation levels of plasma membrane’s phospholipids. The observed remodelling of plasma membrane is in line with ectothermic adaptive responses and gives worms a cumulative advantage to warm temperatures. We have determined that at least six TAX-2/TAX-4 cGMP gated channel expressing sensory neurons and TGF-β/BMP are required for signalling across tissues to modulate fat desaturation. We also find neuronal hsf-1 is not only sufficient but also partially necessary to control the fat remodelling response and for survival at warm temperatures. This is the first study to show that a thermostat-based mechanism can cell non-autonomously coordinate membrane saturation and composition across tissues in a multicellular animal.

SoK: Communication across distributed ledgers - Zamyatin, Alexei; Al-Bassam, Mustafa; Zindros, Dionysis; Kokoris Kogias, Eleftherios; Moreno-Sanchez, Pedro; Kiayias, Aggelos; Knottenbelt, William J. (25th International Conference on Financial Cryptography and Data Security)
Since the inception of Bitcoin, a plethora of distributed ledgers differing in design and purpose has been created. While by design, blockchains provide no means to securely communicate with external systems, numerous attempts towards trustless cross-chain communication have been proposed over the years. Today, cross-chain communication (CCC) plays a fundamental role in cryptocurrency exchanges, scalability efforts via sharding, extension of existing systems through sidechains, and bootstrapping of new blockchains. Unfortunately, existing proposals are designed ad-hoc for specific use-cases, making it hard to gain confidence in their correctness and composability. We provide the first systematic exposition of cross-chain communication protocols. We formalize the underlying research problem and show that CCC is impossible without a trusted third party, contrary to common beliefs in the blockchain community. With this result in mind, we develop a framework to design new and evaluate existing CCC protocols, focusing on the inherent trust assumptions thereof, and derive a classification covering the field of cross-chain communication to date. We conclude by discussing open challenges for CCC research and the implications of interoperability on the security and privacy of blockchains.

Brick: Asynchronous incentive-compatible payment channels - Avarikioti, Zeta; Kokoris Kogias, Eleftherios; Wattenhofer, Roger; Zindros, Dionysis (25th International Conference on Financial Cryptography and Data Security)
Off-chain protocols (channels) are a promising solution to the scalability and privacy challenges of blockchain payments. Current proposals, however, require synchrony assumptions to preserve the safety of a channel, leaking to an adversary the exact amount of time needed to control the network for a successful attack. In this paper, we introduce Brick, the first payment channel that remains secure under network asynchrony and concurrently provides correct incentives. The core idea is to incorporate the conflict resolution process within the channel by introducing a rational committee of external parties, called wardens. Hence, if a party wants to close a channel unilaterally, it can only get the committee’s approval for the last valid state. Additionally, Brick provides sub-second latency because it does not employ heavy-weight consensus. Instead, Brick uses consistent broadcast to announce updates and close the channel, a light-weight abstraction that is powerful enough to preserve safety and liveness to any rational parties. We formally define and prove for Brick the properties a payment channel construction should fulfill. We also design incentives for Brick such that honest and rational behavior aligns. Finally, we provide a reference implementation of the smart contracts in Solidity.

Rational engineering of an erythropoietin fusion protein to treat hypoxia - Lee, Jungmin; Vernet, Andyna; Gruber, Nathalie; Kready, Kasia M.; Burrill, Devin R.; Way, Jeffrey C.; Silver, Pamela A. (Protein Engineering, Design and Selection)
Erythropoietin enhances oxygen delivery and reduces hypoxia-induced cell death, but its pro-thrombotic activity is problematic for use of erythropoietin in treating hypoxia. We constructed a fusion protein that stimulates red blood cell production and neuroprotection without triggering platelet production, a marker for thrombosis. The protein consists of an anti-glycophorin A nanobody and an erythropoietin mutant (L108A). The mutation reduces activation of erythropoietin receptor homodimers that induce erythropoiesis and thrombosis, but maintains the tissue-protective signaling. The binding of the nanobody element to glycophorin A rescues homodimeric erythropoietin receptor activation on red blood cell precursors. In a cell proliferation assay, the fusion protein is active at 10−14 M, allowing an estimate of the number of receptor–ligand complexes needed for signaling. This fusion protein stimulates erythroid cell proliferation in vitro and in mice, and shows neuroprotective activity in vitro. Our erythropoietin fusion protein presents a novel molecule for treating hypoxia.

Special rebranding issue: “Quantitative cell and developmental biology” - Heisenberg, Carl-Philipp J; Lennon, Ana Maria; Mayor, Roberto; Salbreux, Guillaume (Cells and Development)

Theory of branching morphogenesis by local interactions and global guidance - Ucar, Mehmet C; Kamenev, Dmitrii; Sunadome, Kazunori; Fachet, Dominik C; Lallemend, Francois; Adameyko, Igor; Hadjab, Saida; Hannezo, Edouard B (Nature Communications)
Branching morphogenesis governs the formation of many organs such as lung, kidney, and the neurovascular system. Many studies have explored system-specific molecular and cellular regulatory mechanisms, as well as self-organizing rules underlying branching morphogenesis. However, in addition to local cues, branched tissue growth can also be influenced by global guidance. Here, we develop a theoretical framework for a stochastic self-organized branching process in the presence of external cues. Combining analytical theory with numerical simulations, we predict differential signatures of global vs. local regulatory mechanisms on the branching pattern, such as angle distributions, domain size, and space-filling efficiency. We find that branch alignment follows a generic scaling law determined by the strength of global guidance, while local interactions influence the tissue density but not its overall territory. Finally, using zebrafish innervation as a model system, we test these key features of the model experimentally. Our work thus provides quantitative predictions to disentangle the role of different types of cues in shaping branched structures across scales.

Trojan-resilience without cryptography - Chakraborty, Suvradip; Dziembowski, Stefan; Gałązka, Małgorzata; Lizurej, Tomasz; Pietrzak, Krzysztof Z; Yeo, Michelle X
Digital hardware Trojans are integrated circuits whose implementation differ from the specification in an arbitrary and malicious way. For example, the circuit can differ from its specified input/output behavior after some fixed number of queries (known as “time bombs”) or on some particular input (known as “cheat codes”). To detect such Trojans, countermeasures using multiparty computation (MPC) or verifiable computation (VC) have been proposed. On a high level, to realize a circuit with specification F one has more sophisticated circuits F⋄ manufactured (where F⋄ specifies a MPC or VC of F ), and then embeds these F⋄ ’s into a master circuit which must be trusted but is relatively simple compared to F . Those solutions impose a significant overhead as F⋄ is much more complex than F , also the master circuits are not exactly trivial. In this work, we show that in restricted settings, where F has no evolving state and is queried on independent inputs, we can achieve a relaxed security notion using very simple constructions. In particular, we do not change the specification of the circuit at all (i.e., F=F⋄ ). Moreover the master circuit basically just queries a subset of its manufactured circuits and checks if they’re all the same. The security we achieve guarantees that, if the manufactured circuits are initially tested on up to T inputs, the master circuit will catch Trojans that try to deviate on significantly more than a 1/T fraction of the inputs. This bound is optimal for the type of construction considered, and we provably achieve it using a construction where 12 instantiations of F need to be embedded into the master. We also discuss an extremely simple construction with just 2 instantiations for which we conjecture that it already achieves the optimal bound.

Developmental emergence of two-stage nonlinear synaptic integration in cerebellar interneurons - Biane, Celia; Rückerl, Florian; Abrahamsson, Therese; Saint-Cloment, Cécile; Mariani, Jean; Shigemoto, Ryuichi; Digregorio, David A.; Sherrard, Rachel M.; Cathala, Laurence (eLife)
Synaptic transmission, connectivity, and dendritic morphology mature in parallel during brain development and are often disrupted in neurodevelopmental disorders. Yet how these changes influence the neuronal computations necessary for normal brain function are not well understood. To identify cellular mechanisms underlying the maturation of synaptic integration in interneurons, we combined patch-clamp recordings of excitatory inputs in mouse cerebellar stellate cells (SCs), three-dimensional reconstruction of SC morphology with excitatory synapse location, and biophysical modeling. We found that postnatal maturation of postsynaptic strength was homogeneously reduced along the somatodendritic axis, but dendritic integration was always sublinear. However, dendritic branching increased without changes in synapse density, leading to a substantial gain in distal inputs. Thus, changes in synapse distribution, rather than dendrite cable properties, are the dominant mechanism underlying the maturation of neuronal computation. These mechanisms favor the emergence of a spatially compartmentalized two-stage integration model promoting location-dependent integration within dendritic subunits.

Generation of spin currents by a temperature gradient in a two-terminal device - Barfknecht, Rafael E.; Foerster, Angela; Zinner, Nikolaj T.; Volosniev, Artem (Communications Physics)
Theoretical and experimental studies of the interaction between spins and temperature are vital for the development of spin caloritronics, as they dictate the design of future devices. In this work, we propose a two-terminal cold-atom simulator to study that interaction. The proposed quantum simulator consists of strongly interacting atoms that occupy two temperature reservoirs connected by a one-dimensional link. First, we argue that the dynamics in the link can be described using an inhomogeneous Heisenberg spin chain whose couplings are defined by the local temperature. Second, we show the existence of a spin current in a system with a temperature difference by studying the dynamics that follows the spin-flip of an atom in the link. A temperature gradient accelerates the impurity in one direction more than in the other, leading to an overall spin current similar to the spin Seebeck effect.

Interactive analysis of CNN robustness - Sietzen, Stefan; Lechner, Mathias; Borowski, Judy; Hasani, Ramin; Waldner, Manuela (Computer Graphics Forum)
While convolutional neural networks (CNNs) have found wide adoption as state-of-the-art models for image-related tasks, their predictions are often highly sensitive to small input perturbations, which the human vision is robust against. This paper presents Perturber, a web-based application that allows users to instantaneously explore how CNN activations and predictions evolve when a 3D input scene is interactively perturbed. Perturber offers a large variety of scene modifications, such as camera controls, lighting and shading effects, background modifications, object morphing, as well as adversarial attacks, to facilitate the discovery of potential vulnerabilities. Fine-tuned model versions can be directly compared for qualitative evaluation of their robustness. Case studies with machine learning experts have shown that Perturber helps users to quickly generate hypotheses about model vulnerabilities and to qualitatively compare model behavior. Using quantitative analyses, we could replicate users’ insights with other CNN architectures and input images, yielding new insights about the vulnerability of adversarially trained models.

Dissecting organismal morphogenesis by bridging genetics and biophysics - Mishra, Nikhil; Heisenberg, Carl-Philipp J (Annual Review of Genetics)
Multicellular organisms develop complex shapes from much simpler, single-celled zygotes through a process commonly called morphogenesis. Morphogenesis involves an interplay between several factors, ranging from the gene regulatory networks determining cell fate and differentiation to the mechanical processes underlying cell and tissue shape changes. Thus, the study of morphogenesis has historically been based on multidisciplinary approaches at the interface of biology with physics and mathematics. Recent technological advances have further improved our ability to study morphogenesis by bridging the gap between the genetic and biophysical factors through the development of new tools for visualizing, analyzing, and perturbing these factors and their biochemical intermediaries. Here, we review how a combination of genetic, microscopic, biophysical, and biochemical approaches has aided our attempts to understand morphogenesis and discuss potential approaches that may be beneficial to such an inquiry in the future.
Keywords: morphogenesis; forward genetics; high-resolution microscopy; biophysics; biochemistry; patterning

Source data for the manuscript "Theory of branching morphogenesis by local interactions and global guidance" - Ucar, Mehmet C
The zip file includes source data used in the main text of the manuscript "Theory of branching morphogenesis by local interactions and global guidance", as well as a representative Jupyter notebook to reproduce the main figures. A sample script for the simulations of branching and annihilating random walks is also included (Sample_script_for_simulations_of_BARWs.ipynb) to generate exemplary branched networks under external guidance. A detailed description of the simulation setup is provided in the supplementary information of the manuscipt.

Grafting key trees: Efficient key management for overlapping groups - Alwen, Joel F; Auerbach, Benedikt; Baig, Mirza Ahad; Cueto Noval, Miguel; Klein, Karen; Pascual Perez, Guillermo; Pietrzak, Krzysztof Z; Walter, Michael (19th International Conference)
Key trees are often the best solution in terms of transmission cost and storage requirements for managing keys in a setting where a group needs to share a secret key, while being able to efficiently rotate the key material of users (in order to recover from a potential compromise, or to add or remove users). Applications include multicast encryption protocols like LKH (Logical Key Hierarchies) or group messaging like the current IETF proposal TreeKEM. A key tree is a (typically balanced) binary tree, where each node is identified with a key: leaf nodes hold users’ secret keys while the root is the shared group key. For a group of size N, each user just holds log(N) keys (the keys on the path from its leaf to the root) and its entire key material can be rotated by broadcasting 2log(N) ciphertexts (encrypting each fresh key on the path under the keys of its parents). In this work we consider the natural setting where we have many groups with partially overlapping sets of users, and ask if we can find solutions where the cost of rotating a key is better than in the trivial one where we have a separate key tree for each group. We show that in an asymptotic setting (where the number m of groups is fixed while the number N of users grows) there exist more general key graphs whose cost converges to the cost of a single group, thus saving a factor linear in the number of groups over the trivial solution. As our asymptotic “solution” converges very slowly and performs poorly on concrete examples, we propose an algorithm that uses a natural heuristic to compute a key graph for any given group structure. Our algorithm combines two greedy algorithms, and is thus very efficient: it first converts the group structure into a “lattice graph”, which is then turned into a key graph by repeatedly applying the algorithm for constructing a Huffman code. To better understand how far our proposal is from an optimal solution, we prove lower bounds on the update cost of continuous group-key agreement and multicast encryption in a symbolic model admitting (asymmetric) encryption, pseudorandom generators, and secret sharing as building blocks.

Unconventional superconductivity in systems with annular Fermi surfaces: Application to rhombohedral trilayer graphene - Ghazaryan, Areg; Holder, Tobias; Serbyn, Maksym; Berg, Erez (Physical Review Letters)
We show that in a two-dimensional electron gas with an annular Fermi surface, long-range Coulomb interactions can lead to unconventional superconductivity by the Kohn-Luttinger mechanism. Superconductivity is strongly enhanced when the inner and outer Fermi surfaces are close to each other. The most prevalent state has chiral p-wave symmetry, but d-wave and extended s-wave pairing are also possible. We discuss these results in the context of rhombohedral trilayer graphene, where superconductivity was recently discovered in regimes where the normal state has an annular Fermi surface. Using realistic parameters, our mechanism can account for the order of magnitude of Tc, as well as its trends as a function of electron density and perpendicular displacement field. Moreover, it naturally explains some of the outstanding puzzles in this material, that include the weak temperature dependence of the resistivity above Tc, and the proximity of spin singlet superconductivity to the ferromagnetic phase.
Keywords: general physics and astronomy

Fullerene derivatives with oligoethylene-glycol side chains: An investigation on the origin of their outstanding transport properties - Dong, Jingjin; Sami, Selim; Balazs, Daniel; Alessandri, Riccardo; Jahani, Fatimeh; Qiu, Li; Marrink, Siewert J.; Havenith, Remco W.A.; Hummelen, Jan C.; Loi, Maria A.; Portale, Giuseppe (Journal of Materials Chemistry C)
For many years, fullerene derivatives have been the main n-type material of organic electronics and optoelectronics. Recently, fullerene derivatives functionalized with ethylene glycol (EG) side chains have been showing important properties such as enhanced dielectric constants, facile doping and enhanced self-assembly capabilities. Here, we have prepared field-effect transistors using a series of these fullerene derivatives equipped with EG side chains of different lengths. Transport data show the beneficial effect of increasing the EG side chain. In order to understand the material properties, full structural determination of these fullerene derivatives has been achieved by coupling the X-ray data with molecular dynamics (MD) simulations. The increase in transport properties is paired with the formation of extended layered structures, efficient molecular packing and an increase in the crystallite alignment. The layer-like structure is composed of conducting layers, containing of closely packed C60 balls approaching the inter-distance of 1 nm, that are separated by well-defined EG layers, where the EG chains are rather splayed with the chain direction almost perpendicular to the layer normal. Such a layered structure appears highly ordered and highly aligned with the C60 planes oriented parallel to the substrate in the thin film configuration. The order inside the thin film increases with the EG chain length, allowing the systems to achieve mobilities as high as 0.053 cm2 V−1 s−1. Our work elucidates the structure of these interesting semiconducting organic molecules and shows that the synergistic use of X-ray structural analysis and MD simulations is a powerful tool to identify the structure of thin organic films for optoelectronic applications.

Histone H1 prevents non-CG methylation-mediated small RNA biogenesis in Arabidopsis heterochromatin - Choi, Jaemyung; Lyons, David B; Zilberman, Daniel (eLife)
Flowering plants utilize small RNA molecules to guide DNA methyltransferases to genomic sequences. This RNA-directed DNA methylation (RdDM) pathway preferentially targets euchromatic transposable elements. However, RdDM is thought to be recruited by methylation of histone H3 at lysine 9 (H3K9me), a hallmark of heterochromatin. How RdDM is targeted to euchromatin despite an affinity for H3K9me is unclear. Here we show that loss of histone H1 enhances heterochromatic RdDM, preferentially at nucleosome linker DNA. Surprisingly, this does not require SHH1, the RdDM component that binds H3K9me. Furthermore, H3K9me is dispensable for RdDM, as is CG DNA methylation. Instead, we find that non-CG methylation is specifically associated with small RNA biogenesis, and without H1 small RNA production quantitatively expands to non-CG methylated loci. Our results demonstrate that H1 enforces the separation of euchromatic and heterochromatic DNA methylation pathways by excluding the small RNA-generating branch of RdDM from non-CG methylated heterochromatin.
Keywords: genetics and molecular biology

TGFβ signaling in myeloid cells promotes lung and liver metastasis through different mechanisms - Stefanescu, Cristina; Van Gogh, Merel; Roblek, Marko; Heikenwalder, Mathias; Borsig, Lubor (Frontiers in Oncology)
TGFβ overexpression is commonly detected in cancer patients and correlates with poor prognosis and metastasis. Cancer progression is often associated with an enhanced recruitment of myeloid-derived cells to the tumor microenvironment. Here we show that functional TGFβ-signaling in myeloid cells is required for metastasis to the lungs and the liver. Myeloid-specific deletion of Tgfbr2 resulted in reduced spontaneous lung metastasis, which was associated with a reduction of proinflammatory cytokines in the metastatic microenvironment. Notably, CD8+ T cell depletion in myeloid-specific Tgfbr2-deficient mice rescued lung metastasis. Myeloid-specific Tgfbr2-deficiency resulted in reduced liver metastasis with an almost complete absence of myeloid cells within metastatic foci. On contrary, an accumulation of Tgfβ-responsive myeloid cells was associated with an increased recruitment of monocytes and granulocytes and higher proinflammatory cytokine levels in control mice. Monocytic cells isolated from metastatic livers of Tgfbr2-deficient mice showed increased polarization towards the M1 phenotype, Tnfα and Il-1β expression, reduced levels of M2 markers and reduced production of chemokines responsible for myeloid-cell recruitment. No significant differences in Tgfβ levels were observed at metastatic sites of any model. These data demonstrate that Tgfβ signaling in monocytic myeloid cells suppresses CD8+ T cell activity during lung metastasis, while these cells actively contribute to tumor growth during liver metastasis. Thus, myeloid cells modulate metastasis through different mechanisms in a tissue-specific manner.

Bosonization of fermionic many-body dynamics - Benedikter, Niels P; Nam, Phan Thành; Porta, Marcello; Schlein, Benjamin; Seiringer, Robert (Annales Henri Poincaré)
We consider the quantum many-body evolution of a homogeneous Fermi gas in three dimensions in the coupled semiclassical and mean-field scaling regime. We study a class of initial data describing collective particle–hole pair excitations on the Fermi ball. Using a rigorous version of approximate bosonization, we prove that the many-body evolution can be approximated in Fock space norm by a quasi-free bosonic evolution of the collective particle–hole excitations.

Optimal homogenization rates in stochastic homogenization of nonlinear uniformly elliptic equations and systems - Fischer, Julian L; Neukamm, Stefan (Archive for Rational Mechanics and Analysis)
We derive optimal-order homogenization rates for random nonlinear elliptic PDEs with monotone nonlinearity in the uniformly elliptic case. More precisely, for a random monotone operator on \mathbb {R}^d with stationary law (that is spatially homogeneous statistics) and fast decay of correlations on scales larger than the microscale \varepsilon >0, we establish homogenization error estimates of the order \varepsilon in case d\geqq 3, and of the order \varepsilon |\log \varepsilon |^{1/2} in case d=2. Previous results in nonlinear stochastic homogenization have been limited to a small algebraic rate of convergence \varepsilon ^\delta . We also establish error estimates for the approximation of the homogenized operator by the method of representative volumes of the order (L/\varepsilon )^{-d/2} for a representative volume of size L. Our results also hold in the case of systems for which a (small-scale) C^{1,\alpha } regularity theory is available.
Keywords: Mechanical Engineering; Mathematics (miscellaneous); Analysis

On treewidth, separators and Yao’s garbling - Kamath Hosdurg, Chethan; Klein, Karen; Pietrzak, Krzysztof Z (19th International Conference)
We show that Yao’s garbling scheme is adaptively indistinguishable for the class of Boolean circuits of size S and treewidth w with only a SO(w) loss in security. For instance, circuits with constant treewidth are as a result adaptively indistinguishable with only a polynomial loss. This (partially) complements a negative result of Applebaum et al. (Crypto 2013), which showed (assuming one-way functions) that Yao’s garbling scheme cannot be adaptively simulatable. As main technical contributions, we introduce a new pebble game that abstracts out our security reduction and then present a pebbling strategy for this game where the number of pebbles used is roughly O(δwlog(S)) , δ being the fan-out of the circuit. The design of the strategy relies on separators, a graph-theoretic notion with connections to circuit complexity. with only a SO(w) loss in security. For instance, circuits with constant treewidth are as a result adaptively indistinguishable with only a polynomial loss. This (partially) complements a negative result of Applebaum et al. (Crypto 2013), which showed (assuming one-way functions) that Yao’s garbling scheme cannot be adaptively simulatable. As main technical contributions, we introduce a new pebble game that abstracts out our security reduction and then present a pebbling strategy for this game where the number of pebbles used is roughly O(δwlog(S)) , δ being the fan-out of the circuit. The design of the strategy relies on separators, a graph-theoretic notion with connections to circuit complexity.

Duality approach to quantum annealing of the 3-variable exclusive-or satisfiability problem (3-XORSAT) - Medina Ramos, Raimel A; Serbyn, Maksym (Physical Review A)
Classical models with complex energy landscapes represent a perspective avenue for the near-term application of quantum simulators. Until now, many theoretical works studied the performance of quantum algorithms for models with a unique ground state. However, when the classical problem is in a so-called clustering phase, the ground state manifold is highly degenerate. As an example, we consider a 3-XORSAT model defined on simple hypergraphs. The degeneracy of classical ground state manifold translates into the emergence of an extensive number of Z2 symmetries, which remain intact even in the presence of a quantum transverse magnetic field. We establish a general duality approach that restricts the quantum problem to a given sector of conserved Z2 charges and use it to study how the outcome of the quantum adiabatic algorithm depends on the hypergraph geometry. We show that the tree hypergraph which corresponds to a classically solvable instance of the 3-XORSAT problem features a constant gap, whereas the closed hypergraph encounters a second-order phase transition with a gap vanishing as a power-law in the problem size. The duality developed in this work provides a practical tool for studies of quantum models with classically degenerate energy manifold and reveals potential connections between glasses and gauge theories.

All You Need is DAG - Keidar, Idit; Kokoris Kogias, Eleftherios; Naor, Oded; Spiegelman, Alexander (Proceedings of the 2021 ACM Symposium on Principles of Distributed Computing)
We present DAG-Rider, the first asynchronous Byzantine Atomic Broadcast protocol that achieves optimal resilience, optimal amortized communication complexity, and optimal time complexity. DAG-Rider is post-quantum safe and ensures that all values proposed by correct processes eventually get delivered. We construct DAG-Rider in two layers: In the first layer, processes reliably broadcast their proposals and build a structured Directed Acyclic Graph (DAG) of the communication among them. In the second layer, processes locally observe their DAGs and totally order all proposals with no extra communication.

Pipefish locally adapted to low salinity in the Baltic Sea retain phenotypic plasticity to cope with ancestral salinity levels - Goehlich, Henry; Sartoris, Linda; Wagner, Kim-Sara; Wendling, Carolin C.; Roth, Olivia (Frontiers in Ecology and Evolution)
Genetic adaptation and phenotypic plasticity facilitate the migration into new habitats and enable organisms to cope with a rapidly changing environment. In contrast to genetic adaptation that spans multiple generations as an evolutionary process, phenotypic plasticity allows acclimation within the life-time of an organism. Genetic adaptation and phenotypic plasticity are usually studied in isolation, however, only by including their interactive impact, we can understand acclimation and adaptation in nature. We aimed to explore the contribution of adaptation and plasticity in coping with an abiotic (salinity) and a biotic (Vibrio bacteria) stressor using six different populations of the broad-nosed pipefish Syngnathus typhle that originated from either high [14–17 Practical Salinity Unit (PSU)] or low (7–11 PSU) saline environments along the German coastline of the Baltic Sea. We exposed wild caught animals, to either high (15 PSU) or low (7 PSU) salinity, representing native and novel salinity conditions and allowed animals to mate. After male pregnancy, offspring was split and each half was exposed to one of the two salinities and infected with Vibrio alginolyticus bacteria that were evolved at either of the two salinities in a fully reciprocal design. We investigated life-history traits of fathers and expression of 47 target genes in mothers and offspring. Pregnant males originating from high salinity exposed to low salinity were highly susceptible to opportunistic fungi infections resulting in decreased offspring size and number. In contrast, no signs of fungal infection were identified in fathers originating from low saline conditions suggesting that genetic adaptation has the potential to overcome the challenges encountered at low salinity. Offspring from parents with low saline origin survived better at low salinity suggesting genetic adaptation to low salinity. In addition, gene expression analyses of juveniles indicated patterns of local adaptation, trans-generational plasticity and developmental plasticity. In conclusion, our study suggests that pipefish are locally adapted to the low salinity in their environment, however, they are retaining phenotypic plasticity, which allows them to also cope with ancestral salinity levels and prevailing pathogens.
Keywords: ecology; evolution; behavior and systematics; trans-generational plasticity; genetic adaptation; local adaptation; phenotypic plasticity; Baltic Sea; climate change; salinity; syngnathids

Fe2O3 nanoparticles deposited over self-floating facial sponge for facile interfacial seawater solar desalination - Lu, Yuzheng; Arshad, Naila; Irshad, Muhammad Sultan; Ahmed, Iftikhar; Ahmad, Shafiq; Alshahrani, Lina Abdullah; Yousaf, Muhammad; Sayed, Abdelaty Edrees; Nauman, Muhammad (Crystals)
A facile approach for developing an interfacial solar evaporator by heat localization of solar-thermal energy conversion at water-air liquid composed by in-situ polymerization of Fe2O3 nanoparticles (Fe2O3@PPy) deposited over a facial sponge is proposed. The demonstrated system consists of a floating solar receiver having a vertically cross-linked microchannel for wicking up saline water. The in situ polymerized Fe2O3@PPy interfacial layer promotes diffuse reflection and its rough black surface allows Omni-directional solar absorption (94%) and facilitates efficient thermal localization at the water/air interface and offers a defect-rich surface to promote heat localization (41.9 °C) and excellent thermal management due to cellulosic content. The self-floating composite foam reveals continuous vapors generation at a rate of 1.52 kg m−2 h−1 under one 1 kW m−2 and profound evaporating efficiency (95%) without heat losses that dissipates in its surroundings. Indeed, long-term evaporation experiments reveal the negligible disparity in continuous evaporation rate (33.84 kg m−2/8.3 h) receiving two sun solar intensity, and ensures the stability of the device under intense seawater conditions synchronized with excellent salt rejection potential. More importantly, Raman spectroscopy investigation validates the orange dye rejection via Fe2O3@PPy solar evaporator. The combined advantages of high efficiency, self-floating capability, multimedia rejection, low cost, and this configuration are promising for producing large-scale solar steam generating systems appropriate for commercial clean water yield due to their scalable fabrication.

Naïve poison frog tadpoles use bi-modal cues to avoid insect predators but not heterospecific predatory tadpoles - Szabo, B; Mangione, R; Rath, M; Pašukonis, A; Reber, SA; Oh, Jinook; Ringler, M; Ringler, E (Journal of Experimental Biology)
For animals to survive until reproduction, it is crucial that juveniles successfully detect potential predators and respond with appropriate behavior. The recognition of cues originating from predators can be innate or learned. Cues of various modalities might be used alone or in multi-modal combinations to detect and distinguish predators but studies investigating multi-modal integration in predator avoidance are scarce. Here, we used wild, naive tadpoles of the Neotropical poison frog Allobates femoralis ( Boulenger, 1884) to test their reaction to cues with two modalities from two different sympatrically occurring potential predators: heterospecific predatory Dendrobates tinctorius tadpoles and dragonfly larvae. We presented A. femoralis tadpoles with olfactory or visual cues, or a combination of the two, and compared their reaction to a water control in a between-individual design. In our trials, A. femoralis tadpoles reacted to multi-modal stimuli (a combination of visual and chemical information) originating from dragonfly larvae with avoidance but showed no reaction to uni-modal cues or cues from heterospecific tadpoles. In addition, visual cues from conspecifics increased swimming activity while cues from predators had no effect on tadpole activity. Our results show that A. femoralis tadpoles can innately recognize some predators and probably need both visual and chemical information to effectively avoid them. This is the first study looking at anti-predator behavior in poison frog tadpoles. We discuss how parental care might influence the expression of predator avoidance responses in tadpoles.

On the dynamic slip boundary condition for Navier-Stokes-like problems - Abbatiello, Anna; Bulíček, Miroslav; Maringová, Erika (Mathematical Models and Methods in Applied Sciences)
The choice of the boundary conditions in mechanical problems has to reflect the interaction of the considered material with the surface. Still the assumption of the no-slip condition is preferred in order to avoid boundary terms in the analysis and slipping effects are usually overlooked. Besides the “static slip models”, there are phenomena that are not accurately described by them, e.g. at the moment when the slip changes rapidly, the wall shear stress and the slip can exhibit a sudden overshoot and subsequent relaxation. When these effects become significant, the so-called dynamic slip phenomenon occurs. We develop a mathematical analysis of Navier–Stokes-like problems with a dynamic slip boundary condition, which requires a proper generalization of the Gelfand triplet and the corresponding function space setting.

The effect of geometry and illumination on appearance perception of different material categories - Chen, Bin; Wang, Chao; Piovarci, Michael; Seidel, Hans Peter; Didyk, Piotr; Myszkowski, Karol; Serrano, Ana (Visual Computer)
The understanding of material appearance perception is a complex problem due to interactions between material reflectance, surface geometry, and illumination. Recently, Serrano et al. collected the largest dataset to date with subjective ratings of material appearance attributes, including glossiness, metallicness, sharpness and contrast of reflections. In this work, we make use of their dataset to investigate for the first time the impact of the interactions between illumination, geometry, and eight different material categories in perceived appearance attributes. After an initial analysis, we select for further analysis the four material categories that cover the largest range for all perceptual attributes: fabric, plastic, ceramic, and metal. Using a cumulative link mixed model (CLMM) for robust regression, we discover interactions between these material categories and four representative illuminations and object geometries. We believe that our findings contribute to expanding the knowledge on material appearance perception and can be useful for many applications, such as scene design, where any particular material in a given shape can be aligned with dominant classes of illumination, so that a desired strength of appearance attributes can be achieved.

Extracellular hyaluronate pressure shaped by cellular tethers drives tissue morphogenesis - Munjal, Akankshi; Hannezo, Edouard B; Tsai, Tony Y.C.; Mitchison, Timothy J.; Megason, Sean G. (Cell)
How tissues acquire complex shapes is a fundamental question in biology and regenerative medicine. Zebrafish semicircular canals form from invaginations in the otic epithelium (buds) that extend and fuse to form the hubs of each canal. We find that conventional actomyosin-driven behaviors are not required. Instead, local secretion of hyaluronan, made by the enzymes uridine 5′-diphosphate dehydrogenase (ugdh) and hyaluronan synthase 3 (has3), drives canal morphogenesis. Charged hyaluronate polymers osmotically swell with water and generate isotropic extracellular pressure to deform the overlying epithelium into buds. The mechanical anisotropy needed to shape buds into tubes is conferred by a polarized distribution of actomyosin and E-cadherin-rich membrane tethers, which we term cytocinches. Most work on tissue morphogenesis ascribes actomyosin contractility as the driving force, while the extracellular matrix shapes tissues through differential stiffness. Our work inverts this expectation. Hyaluronate pressure shaped by anisotropic tissue stiffness may be a widespread mechanism for powering morphological change in organogenesis and tissue engineering.

Determinacy in discrete-bidding infinite-duration games - Aghajohari, Milad; Avni, Guy; Henzinger, Thomas A (Logical Methods in Computer Science)
In two-player games on graphs, the players move a token through a graph to produce an infinite path, which determines the winner of the game. Such games are central in formal methods since they model the interaction between a non-terminating system and its environment. In bidding games the players bid for the right to move the token: in each round, the players simultaneously submit bids, and the higher bidder moves the token and pays the other player. Bidding games are known to have a clean and elegant mathematical structure that relies on the ability of the players to submit arbitrarily small bids. Many applications, however, require a fixed granularity for the bids, which can represent, for example, the monetary value expressed in cents. We study, for the first time, the combination of discrete-bidding and infinite-duration games. Our most important result proves that these games form a large determined subclass of concurrent games, where determinacy is the strong property that there always exists exactly one player who can guarantee winning the game. In particular, we show that, in contrast to non-discrete bidding games, the mechanism with which tied bids are resolved plays an important role in discrete-bidding games. We study several natural tie-breaking mechanisms and show that, while some do not admit determinacy, most natural mechanisms imply determinacy for every pair of initial budgets.
Keywords: computer science; computer science and game theory; logic in computer science

Reverse firewalls for adaptively secure MPC without setup - Chakraborty, Suvradip; Ganesh, Chaya; Pancholi, Mahak; Sarkar, Pratik (27th International Conference on the Theory and Application of Cryptology and Information Security)
We study Multi-party computation (MPC) in the setting of subversion, where the adversary tampers with the machines of honest parties. Our goal is to construct actively secure MPC protocols where parties are corrupted adaptively by an adversary (as in the standard adaptive security setting), and in addition, honest parties’ machines are compromised. The idea of reverse firewalls (RF) was introduced at EUROCRYPT’15 by Mironov and Stephens-Davidowitz as an approach to protecting protocols against corruption of honest parties’ devices. Intuitively, an RF for a party P is an external entity that sits between P and the outside world and whose scope is to sanitize P ’s incoming and outgoing messages in the face of subversion of their computer. Mironov and Stephens-Davidowitz constructed a protocol for passively-secure two-party computation. At CRYPTO’20, Chakraborty, Dziembowski and Nielsen constructed a protocol for secure computation with firewalls that improved on this result, both by extending it to multi-party computation protocol, and considering active security in the presence of static corruptions. In this paper, we initiate the study of RF for MPC in the adaptive setting. We put forward a definition for adaptively secure MPC in the reverse firewall setting, explore relationships among the security notions, and then construct reverse firewalls for MPC in this stronger setting of adaptive security. We also resolve the open question of Chakraborty, Dziembowski and Nielsen by removing the need for a trusted setup in constructing RF for MPC. Towards this end, we construct reverse firewalls for adaptively secure augmented coin tossing and adaptively secure zero-knowledge protocols and obtain a constant round adaptively secure MPC protocol in the reverse firewall setting without setup. Along the way, we propose a new multi-party adaptively secure coin tossing protocol in the plain model, that is of independent interest.

Combined effect of cell geometry and polarity domains determines the orientation of unequal division - Godard, Benoit G; Dumollard, Remi; Heisenberg, Carl-Philipp J; Mcdougall, Alex (eLife)
Cell division orientation is thought to result from a competition between cell geometry and polarity domains controlling the position of the mitotic spindle during mitosis. Depending on the level of cell shape anisotropy or the strength of the polarity domain, one dominates the other and determines the orientation of the spindle. Whether and how such competition is also at work to determine unequal cell division (UCD), producing daughter cells of different size, remains unclear. Here, we show that cell geometry and polarity domains cooperate, rather than compete, in positioning the cleavage plane during UCDs in early ascidian embryos. We found that the UCDs and their orientation at the ascidian third cleavage rely on the spindle tilting in an anisotropic cell shape, and cortical polarity domains exerting different effects on spindle astral microtubules. By systematically varying mitotic cell shape, we could modulate the effect of attractive and repulsive polarity domains and consequently generate predicted daughter cell size asymmetries and position. We therefore propose that the spindle position during UCD is set by the combined activities of cell geometry and polarity domains, where cell geometry modulates the effect of cortical polarity domain(s).

Toll-like receptor 4 deficiency facilitates α-synuclein propagation and neurodegeneration in a mouse model of prodromal Parkinson's disease - Venezia, Serena; Kaufmann, Walter; Wenning, Gregor K.; Stefanova, Nadia (Parkinsonism & Related Disorders)
The evidence linking innate immunity mechanisms and neurodegenerative diseases is growing, but the specific mechanisms are incompletely understood. Experimental data suggest that microglial TLR4 mediates the uptake and clearance of α-synuclein also termed synucleinophagy. The accumulation of misfolded α-synuclein throughout the brain is central to Parkinson's disease (PD). The distribution and progression of the pathology is often attributed to the propagation of α-synuclein. Here, we apply a classical α-synuclein propagation model of prodromal PD in wild type and TLR4 deficient mice to study the role of TLR4 in the progression of the disease. Our data suggest that TLR4 deficiency facilitates the α-synuclein seed spreading associated with reduced lysosomal activity of microglia. Three months after seed inoculation, more pronounced proteinase K-resistant α-synuclein inclusion pathology is observed in mice with TLR4 deficiency. The facilitated propagation of α-synuclein is associated with early loss of dopamine transporter (DAT) signal in the striatum and loss of dopaminergic neurons in substantia nigra pars compacta of TLR4 deficient mice. These new results support TLR4 signaling as a putative target for disease modification to slow the progression of PD and related disorders.

Shadow surface states in topological Kondo insulators - Ghazaryan, Areg; Nica, Emilian M.; Erten, Onur; Ghaemi, Pouyan (New Journal of Physics)
The surface states of 3D topological insulators in general have negligible quantum oscillations (QOs) when the chemical potential is tuned to the Dirac points. In contrast, we find that topological Kondo insulators (TKIs) can support surface states with an arbitrarily large Fermi surface (FS) when the chemical potential is pinned to the Dirac point. We illustrate that these FSs give rise to finite-frequency QOs, which can become comparable to the extremal area of the unhybridized bulk bands. We show that this occurs when the crystal symmetry is lowered from cubic to tetragonal in a minimal two-orbital model. We label such surface modes as 'shadow surface states'. Moreover, we show that the sufficient next-nearest neighbor out-of-plane hybridization leading to shadow surface states can be self-consistently stabilized for tetragonal TKIs. Consequently, shadow surface states provide an important example of high-frequency QOs beyond the context of cubic TKIs.

Excited rotational states of molecules in a superfluid - Cherepanov, Igor; Bighin, Giacomo; Schouder, Constant A.; Chatterley, Adam S.; Albrechtsen, Simon H.; Muñoz, Alberto Viñas; Christiansen, Lars; Stapelfeldt, Henrik; Lemeshko, Mikhail (Physical Review A)
We combine experimental and theoretical approaches to explore excited rotational states of molecules embedded in helium nanodroplets using CS2 and I2 as examples. Laser-induced nonadiabatic molecular alignment is employed to measure spectral lines for rotational states extending beyond those initially populated at the 0.37 K droplet temperature. We construct a simple quantum-mechanical model, based on a linear rotor coupled to a single-mode bosonic bath, to determine the rotational energy structure in its entirety. The calculated and measured spectral lines are in good agreement. We show that the effect of the surrounding superfluid on molecular rotation can be rationalized by a single quantity, the angular momentum, transferred from the molecule to the droplet.

Sparse multi-decoder recursive projection aggregation for Reed-Muller codes - Fathollahi, Dorsa; Farsad, Nariman; Hashemi, Seyyed Ali; Mondelli, Marco (2021 IEEE International Symposium on Information Theory)
We thank Emmanuel Abbe and Min Ye for providing us the implementation of RPA decoding. D. Fathollahi and M. Mondelli are partially supported by the 2019 Lopez-Loreta Prize. N. Farsad is supported by Discovery Grant from the Natural Sciences and Engineering Research Council of Canada (NSERC) and Canada Foundation for Innovation (CFI), John R. Evans Leader Fund. S. A. Hashemi is supported by a Postdoctoral Fellowship from NSERC.

Adversarial training is not ready for robot learning - Lechner, Mathias; Hasani, Ramin; Grosu, Radu; Rus, Daniela; Henzinger, Thomas A (2021 IEEE International Conference on Robotics and Automation)
Adversarial training is an effective method to train deep learning models that are resilient to norm-bounded perturbations, with the cost of nominal performance drop. While adversarial training appears to enhance the robustness and safety of a deep model deployed in open-world decision-critical applications, counterintuitively, it induces undesired behaviors in robot learning settings. In this paper, we show theoretically and experimentally that neural controllers obtained via adversarial training are subjected to three types of defects, namely transient, systematic, and conditional errors. We first generalize adversarial training to a safety-domain optimization scheme allowing for more generic specifications. We then prove that such a learning process tends to cause certain error profiles. We support our theoretical results by a thorough experimental safety analysis in a robot-learning task. Our results suggest that adversarial training is not yet ready for robot learning.

The distribution of the maximum of partial sums of Kloosterman sums and other trace functions - Autissier, Pascal; Bonolis, Dante; Lamzouri, Youness (Compositio Mathematica)
In this paper, we investigate the distribution of the maximum of partial sums of families of m -periodic complex-valued functions satisfying certain conditions. We obtain precise uniform estimates for the distribution function of this maximum in a near-optimal range. Our results apply to partial sums of Kloosterman sums and other families of ℓ -adic trace functions, and are as strong as those obtained by Bober, Goldmakher, Granville and Koukoulopoulos for character sums. In particular, we improve on the recent work of the third author for Birch sums. However, unlike character sums, we are able to construct families of m -periodic complex-valued functions which satisfy our conditions, but for which the Pólya–Vinogradov inequality is sharp.
Keywords: Algebra and Number Theory

Tidying up the mess - Liu, Yu; Ibáñez, Maria (Science)
Thermoelectric materials are engines that convert heat into an electrical current. Intuitively, the efficiency of this process depends on how many electrons (charge carriers) can move and how easily they do so, how much energy those moving electrons transport, and how easily the temperature gradient is maintained. In terms of material properties, an excellent thermoelectric material requires a high electrical conductivity σ, a high Seebeck coefficient S (a measure of the induced thermoelectric voltage as a function of temperature gradient), and a low thermal conductivity κ. The challenge is that these three properties are strongly interrelated in a conflicting manner (1). On page 722 of this issue, Roychowdhury et al. (2) have found a way to partially break these ties in silver antimony telluride (AgSbTe2) with the addition of cadmium (Cd) cations, which increase the ordering in this inherently disordered thermoelectric material.
Keywords: multidisciplinary

Enhanced thermoelectric performance of n-type Bi2Se3 nanosheets through Sn doping - Li, Mengyao; Zhang, Yu; Zhang, Ting; Zuo, Yong; Xiao, Ke; Arbiol, Jordi; Llorca, Jordi; Liu, Yu; Cabot, Andreu (Nanomaterials)
The cost-effective conversion of low-grade heat into electricity using thermoelectric devices requires developing alternative materials and material processing technologies able to reduce the currently high device manufacturing costs. In this direction, thermoelectric materials that do not rely on rare or toxic elements such as tellurium or lead need to be produced using high-throughput technologies not involving high temperatures and long processes. Bi2Se3 is an obvious possible Te-free alternative to Bi2Te3 for ambient temperature thermoelectric applications, but its performance is still low for practical applications, and additional efforts toward finding proper dopants are required. Here, we report a scalable method to produce Bi2Se3 nanosheets at low synthesis temperatures. We studied the influence of different dopants on the thermoelectric properties of this material. Among the elements tested, we demonstrated that Sn doping resulted in the best performance. Sn incorporation resulted in a significant improvement to the Bi2Se3 Seebeck coefficient and a reduction in the thermal conductivity in the direction of the hot-press axis, resulting in an overall 60% improvement in the thermoelectric figure of merit of Bi2Se3.
Keywords: General Materials Science; General Chemical Engineering

Loss of Hem1 disrupts macrophage function and impacts migration, phagocytosis, and integrin-mediated adhesion - Stahnke, Stephanie; Döring, Hermann; Kusch, Charly; de Gorter, David J.J.; Dütting, Sebastian; Guledani, Aleks; Pleines, Irina; Schnoor, Michael; Sixt, Michael K; Geffers, Robert; Rohde, Manfred; Müsken, Mathias; et al. (Current Biology)
Hematopoietic-specific protein 1 (Hem1) is an essential subunit of the WAVE regulatory complex (WRC) in immune cells. WRC is crucial for Arp2/3 complex activation and the protrusion of branched actin filament networks. Moreover, Hem1 loss of function in immune cells causes autoimmune diseases in humans. Here, we show that genetic removal of Hem1 in macrophages diminishes frequency and efficacy of phagocytosis as well as phagocytic cup formation in addition to defects in lamellipodial protrusion and migration. Moreover, Hem1-null macrophages displayed strong defects in cell adhesion despite unaltered podosome formation and concomitant extracellular matrix degradation. Specifically, dynamics of both adhesion and de-adhesion as well as concomitant phosphorylation of paxillin and focal adhesion kinase (FAK) were significantly compromised. Accordingly, disruption of WRC function in non-hematopoietic cells coincided with both defects in adhesion turnover and altered FAK and paxillin phosphorylation. Consistently, platelets exhibited reduced adhesion and diminished integrin αIIbβ3 activation upon WRC removal. Interestingly, adhesion phenotypes, but not lamellipodia formation, were partially rescued by small molecule activation of FAK. A full rescue of the phenotype, including lamellipodia formation, required not only the presence of WRCs but also their binding to and activation by Rac. Collectively, our results uncover that WRC impacts on integrin-dependent processes in a FAK-dependent manner, controlling formation and dismantling of adhesions, relevant for properly grabbing onto extracellular surfaces and particles during cell edge expansion, like in migration or phagocytosis.
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

Improved deterministic (Δ+1) coloring in low-space MPC - Czumaj, Artur; Davies, Peter; Parter, Merav (Proceedings of the 2021 ACM Symposium on Principles of Distributed Computing)
We present a deterministic O(log log log n)-round low-space Massively Parallel Computation (MPC) algorithm for the classical problem of (Δ+1)-coloring on n-vertex graphs. In this model, every machine has sublinear local space of size n^φ for any arbitrary constant φ \in (0,1). Our algorithm works under the relaxed setting where each machine is allowed to perform exponential local computations, while respecting the n^φ space and bandwidth limitations. Our key technical contribution is a novel derandomization of the ingenious (Δ+1)-coloring local algorithm by Chang-Li-Pettie (STOC 2018, SIAM J. Comput. 2020). The Chang-Li-Pettie algorithm runs in T_local =poly(loglog n) rounds, which sets the state-of-the-art randomized round complexity for the problem in the local model. Our derandomization employs a combination of tools, notably pseudorandom generators (PRG) and bounded-independence hash functions. The achieved round complexity of O(logloglog n) rounds matches the bound of log(T_local ), which currently serves an upper bound barrier for all known randomized algorithms for locally-checkable problems in this model. Furthermore, no deterministic sublogarithmic low-space MPC algorithms for the (Δ+1)-coloring problem have been known before.

On the volume of sections of the cube - Ivanov, Grigory; Tsiutsiurupa, Igor (Analysis and Geometry in Metric Spaces)
We study the properties of the maximal volume k-dimensional sections of the n-dimensional cube [−1, 1]n. We obtain a first order necessary condition for a k-dimensional subspace to be a local maximizer of the volume of such sections, which we formulate in a geometric way. We estimate the length of the projection of a vector of the standard basis of Rn onto a k-dimensional subspace that maximizes the volume of the intersection. We nd the optimal upper bound on the volume of a planar section of the cube [−1, 1]n , n ≥ 2.
Keywords: Applied Mathematics; Geometry and Topology; Analysis

Component stability in low-space massively parallel computation - Czumaj, Artur; Davies, Peter; Parter, Merav (Proceedings of the 2021 ACM Symposium on Principles of Distributed Computing)
In this paper, we study the power and limitations of component-stable algorithms in the low-space model of Massively Parallel Computation (MPC). Recently Ghaffari, Kuhn and Uitto (FOCS 2019) introduced the class of component-stable low-space MPC algorithms, which are, informally, defined as algorithms for which the outputs reported by the nodes in different connected components are required to be independent. This very natural notion was introduced to capture most (if not all) of the known efficient MPC algorithms to date, and it was the first general class of MPC algorithms for which one can show non-trivial conditional lower bounds. In this paper we enhance the framework of component-stable algorithms and investigate its effect on the complexity of randomized and deterministic low-space MPC. Our key contributions include: 1) We revise and formalize the lifting approach of Ghaffari, Kuhn and Uitto. This requires a very delicate amendment of the notion of component stability, which allows us to fill in gaps in the earlier arguments. 2) We also extend the framework to obtain conditional lower bounds for deterministic algorithms and fine-grained lower bounds that depend on the maximum degree Δ. 3) We demonstrate a collection of natural graph problems for which non-component-stable algorithms break the conditional lower bound obtained for component-stable algorithms. This implies that, for both deterministic and randomized algorithms, component-stable algorithms are conditionally weaker than the non-component-stable ones. Altogether our results imply that component-stability might limit the computational power of the low-space MPC model, paving the way for improved upper bounds that escape the conditional lower bound setting of Ghaffari, Kuhn, and Uitto.

Self-adjoint extensions of bipartite Hamiltonians - Lenz, Daniel; Weinmann, Timon; Wirth, Melchior (Proceedings of the Edinburgh Mathematical Society)
We compute the deficiency spaces of operators of the form 𝐻𝐴⊗̂ 𝐼+𝐼⊗̂ 𝐻𝐵, for symmetric 𝐻𝐴 and self-adjoint 𝐻𝐵. This enables us to construct self-adjoint extensions (if they exist) by means of von Neumann's theory. The structure of the deficiency spaces for this case was asserted already in Ibort et al. [Boundary dynamics driven entanglement, J. Phys. A: Math. Theor. 47(38) (2014) 385301], but only proven under the restriction of 𝐻𝐵 having discrete, non-degenerate spectrum.

Correlation energy of a weakly interacting Fermi gas - Benedikter, Niels P; Nam, Phan Thành; Porta, Marcello; Schlein, Benjamin; Seiringer, Robert (Inventiones Mathematicae)
We derive rigorously the leading order of the correlation energy of a Fermi gas in a scaling regime of high density and weak interaction. The result verifies the prediction of the random-phase approximation. Our proof refines the method of collective bosonization in three dimensions. We approximately diagonalize an effective Hamiltonian describing approximately bosonic collective excitations around the Hartree–Fock state, while showing that gapless and non-collective excitations have only a negligible effect on the ground state energy.

Spectral signatures of population III and envelope-stripped stars in galaxies at the epoch of reionization - Berzin, Elizabeth; Secunda, Amy; Cen, Renyue; Menegas, Alexander; Götberg, Ylva Louise Linsdotter (The Astrophysical Journal)
While most simulations of the epoch of reionization have focused on single-stellar populations in star-forming dwarf galaxies, products of binary evolution are expected to significantly contribute to emissions of hydrogen-ionizing photons. Among these products are stripped stars (or helium stars), which have their envelopes stripped from interactions with binary companions, leaving an exposed helium core. Previous work has suggested these stripped stars can dominate the Lyman Continuum (LyC) photon output of high-redshift, low-luminosity galaxies post-starburst. Other sources of hard radiation in the early universe include zero-metallicity Population iii stars, which may have similar spectral energy distribution (SED) properties to galaxies with radiation dominated by stripped-star emissions. Here, we use four metrics (the power-law exponent over wavelength intervals 240–500 Å, 600–900 Å, and 1200–2000 Å, and the ratio of total luminosity in FUV wavelengths to LyC wavelengths) to compare the SEDs of simulated galaxies with only single-stellar evolution, galaxies containing stripped stars, and galaxies containing Population iii stars, with four different initial mass functions (IMFs). We find that stripped stars significantly alter SEDs in the LyC range of galaxies at the epoch of reionization. SEDs in galaxies with stripped stars have lower power-law indices in the LyC range and lower FUV to LyC luminosity ratios. These differences in SEDs are present at all considered luminosities (${M}_{UV}\gt -15$, AB system), and are most pronounced for lower-luminosity galaxies. Intrinsic SEDs as well as those with interstellar medium absorption of galaxies with stripped stars and Population iii stars are found to be distinct for all tested Population iii IMFs.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Binary-stripped stars as core-collapse supernovae progenitors - Vartanyan, David; Laplace, Eva; Renzo, Mathieu; Götberg, Ylva Louise Linsdotter; Burrows, Adam; de Mink, Selma E. (The Astrophysical Journal Letters)
Most massive stars experience binary interactions in their lifetimes that can alter both the surface and core structure of the stripped star with significant effects on their ultimate fate as core-collapse supernovae. However, core-collapse supernovae simulations to date have focused almost exclusively on the evolution of single stars. We present a systematic simulation study of single and binary-stripped stars with the same initial mass as candidates for core-collapse supernovae (11–21 M⊙). Generally, we find that binary-stripped stars core tend to have a smaller compactness parameter, with a more prominent, deeper silicon/oxygen interface, and explode preferentially to the corresponding single stars of the same initial mass. Such a dichotomy of behavior between these two modes of evolution would have important implications for supernovae statistics, including the final neutron star masses, explosion energies, and nucleosynthetic yields. Binary-stripped remnants are also well poised to populate the possible mass gap between the heaviest neutron stars and the lightest black holes. Our work presents an improvement along two fronts, as we self-consistently account for the pre-collapse stellar evolution and the subsequent explosion outcome. Even so, our results emphasize the need for more detailed stellar evolutionary models to capture the sensitive nature of explosion outcome.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

The detection and characterization of Be+sdO binaries from HST/STIS FUV spectroscopy - Wang, Luqian; Gies, Douglas R.; Peters, Geraldine J.; Götberg, Ylva Louise Linsdotter; Chojnowski, S. Drew; Lester, Kathryn V.; Howell, Steve B. (The Astronomical Journal)
The B emission-line stars are rapid rotators that were probably spun up by mass and angular momentum accretion through mass transfer in an interacting binary. Mass transfer will strip the donor star of its envelope to create a small and hot subdwarf remnant. Here we report on Hubble Space Telescope/STIS far-ultraviolet spectroscopy of a sample of Be stars that reveals the presence of the hot sdO companion through the calculation of cross-correlation functions of the observed and model spectra. We clearly detect the spectral signature of the sdO star in 10 of the 13 stars in the sample, and the spectral signals indicate that the sdO stars are hot, relatively faint, and slowly rotating as predicted by models. A comparison of their temperatures and radii with evolutionary tracks indicates that the sdO stars occupy the relatively long-lived, He-core burning stage. Only 1 of the 10 detections was a known binary prior to this investigation, which emphasizes the difficulty of finding such Be+sdO binaries through optical spectroscopy. However, these results and others indicate that many Be stars probably host hot subdwarf companions.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

The young massive SMC cluster NGC 330 seen by MUSE. II. Multiplicity properties of the massive-star population - Bodensteiner, J.; Sana, H.; Wang, C.; Langer, N.; Mahy, L.; Banyard, G.; de Koter, A.; de Mink, S. E.; Evans, C. J.; Götberg, Ylva Louise Linsdotter; Patrick, L. R.; Schneider, F. R. N.; et al. (Astronomy & Astrophysics)
Context. Observations of massive stars in open clusters younger than ∼8 Myr have shown that a majority of them are in binary systems, most of which will interact during their life. While these can be used as a proxy of the initial multiplicity properties, studying populations of massive stars older than ∼20 Myr allows us to probe the outcome of these interactions after a significant number of systems have experienced mass and angular momentum transfer and may even have merged. Aims. Using multi-epoch integral-field spectroscopy, we aim to investigate the multiplicity properties of the massive-star population in the dense core of the ∼40 Myr old cluster NGC 330 in the Small Magellanic Cloud in order to search for possible imprints of stellar evolution on the multiplicity properties. Methods. We obtained six epochs of VLT/MUSE observations operated in wide-field mode with the extended wavelength setup and supported by adaptive optics. We extracted spectra and measured radial velocities for stars brighter than mF814W = 19. We identified single-lined spectroscopic binaries through significant RV variability with a peak-to-peak amplitude larger than 20 km s−1. We also identified double-lined spectroscopic binaries, and quantified the observational biases for binary detection. In particular, we took into account that binary systems with similar line strengths are difficult to detect in our data set. Results. The observed spectroscopic binary fraction among stars brighter than mF814W = 19 (approximately 5.5 M⊙ on the main sequence) is fSBobs = 13.2 ± 2.0%. Considering period and mass ratio ranges from log(P) = 0.15−3.5 (about 1.4 to 3160 d), q = 0.1−1.0, and a representative set of orbital parameter distributions, we find a bias-corrected close binary fraction of fcl = 34−7+8%. This fraction seems to decline for the fainter stars, which indicates either that the close binary fraction drops in the B-type domain, or that the period distribution becomes more heavily weighted toward longer orbital periods. We further find that both fractions vary strongly in different regions of the color-magnitude diagram, which corresponds to different evolutionary stages. This probably reveals the imprint of the binary history of different groups of stars. In particular, we find that the observed spectroscopic binary fraction of Be stars (fSBobs = 2 ± 2%) is significantly lower than that of B-type stars (fSBobs = 9 ± 2%). Conclusions. We provide the first homogeneous radial velocity study of a large sample of B-type stars at a low metallicity ([Fe/H] ≲ −1.0). The overall bias-corrected close binary fraction (log(P) < 3.5 d) of the B-star population in NGC 330 is lower than the fraction reported for younger Galactic and Large Magellanic Cloud clusters in previous works. More data are needed, however, to establish whether the observed differences are caused by an age or a metallicity effect.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Different to the core: The pre-supernova structures of massive single and binary-stripped stars - Laplace, E.; Justham, S.; Renzo, M.; Götberg, Ylva Louise Linsdotter; Farmer, R.; Vartanyan, D.; de Mink, S. E. (Astronomy & Astrophysics)
The majority of massive stars live in binary or multiple systems and will interact with a companion during their lifetimes, which helps to explain the observed diversity of core-collapse supernovae. Donor stars in binary systems can lose most of their hydrogen-rich envelopes through mass transfer. As a result, not only are the surface properties affected, but so is the core structure. However, most calculations of the core-collapse properties of massive stars rely on single-star models. We present a systematic study of the difference between the pre-supernova structures of single stars and stars of the same initial mass (11–21 M⊙) that have been stripped due to stable post-main-sequence mass transfer at solar metallicity. We present the pre-supernova core composition with novel diagrams that give an intuitive representation of the isotope distribution. As shown in previous studies, at the edge of the carbon-oxygen core, the binary-stripped star models contain an extended gradient of carbon, oxygen, and neon. This layer remains until core collapse and is more extended in mass for higher initial stellar masses. It originates from the receding of the convective helium core during core helium burning in binary-stripped stars, which does not occur in single-star models. We find that this same evolutionary phase leads to systematic differences in the final density and nuclear energy generation profiles. Binary-stripped star models have systematically higher total masses of carbon at the moment of core collapse compared to single-star models, which likely results in systematically different supernova yields. In about half of our models, the silicon-burning and oxygen-rich layers merge after core silicon burning. We discuss the implications of our findings for the “explodability”, supernova observations, and nucleosynthesis of these stars. Our models are publicly available and can be readily used as input for detailed supernova simulations.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Pre-explosion properties of Helium star donors to thermonuclear supernovae - Wong, Tin Long Sunny; Schwab, Josiah; Götberg, Ylva Louise Linsdotter (The Astrophysical Journal)
Helium star–carbon-oxygen white dwarf (CO WD) binaries are potential single-degenerate progenitor systems of thermonuclear supernovae. Revisiting a set of binary evolution calculations using the stellar evolution code MESA, we refine our previous predictions about which systems can lead to a thermonuclear supernova and then characterize the properties of the helium star donor at the time of explosion. We convert these model properties to near-UV/optical magnitudes assuming a blackbody spectrum and support this approach using a matched stellar atmosphere model. These models will be valuable to compare with pre-explosion imaging for future supernovae, though we emphasize the observational difficulty of detecting extremely blue companions. The pre-explosion source detected in association with SN 2012Z has been interpreted as a helium star binary containing an initially ultra-massive WD in a multiday orbit. However, extending our binary models to initial CO WD masses of up to 1.2 M⊙, we find that these systems undergo off-center carbon ignitions and thus are not expected to produce thermonuclear supernovae. This tension suggests that, if SN 2012Z is associated with a helium star–WD binary, then the pre-explosion optical light from the system must be significantly modified by the binary environment and/or the WD does not have a carbon-rich interior composition.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Evolution of accretor stars in massive binaries: Broader implications from modeling ζ Ophiuchi - Renzo, M.; Götberg, Ylva Louise Linsdotter (The Astrophysical Journal)
Most massive stars are born in binaries close enough for mass transfer episodes. These modify the appearance, structure, and future evolution of both stars. We compute the evolution of a 100-day-period binary, consisting initially of a 25 M⊙ star and a 17 M⊙ star, which experiences stable mass transfer. We focus on the impact of mass accretion on the surface composition, internal rotation, and structure of the accretor. To anchor our models, we show that our accretor broadly reproduces the properties of ζ Ophiuchi, which has long been proposed to have accreted mass before being ejected as a runaway star when the companion exploded. We compare our accretor to models of single rotating stars and find that the later and stronger spin-up provided by mass accretion produces significant differences. Specifically, the core of the accretor retains higher spin at the end of the main sequence, and a convective layer develops that changes its density profile. Moreover, the surface of the accretor star is polluted by CNO-processed material donated by the companion. Our models show effects of mass accretion in binaries that are not captured in single rotating stellar models. This possibly impacts the further evolution (either in a binary or as single stars), the final collapse, and the resulting spin of the compact object.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

All-optical probe of three-dimensional topological insulators based on high-harmonic generation by circularly polarized laser fields - Baykusheva, Denitsa Rangelova; Chacón, Alexis; Lu, Jian; Bailey, Trevor P.; Sobota, Jonathan A.; Soifer, Hadas; Kirchmann, Patrick S.; Rotundu, Costel; Uher, Ctirad; Heinz, Tony F.; Reis, David A.; Ghimire, Shambhu (Nano Letters)
We report the observation of an anomalous nonlinear optical response of the prototypical three-dimensional topological insulator bismuth selenide through the process of high-order harmonic generation. We find that the generation efficiency increases as the laser polarization is changed from linear to elliptical, and it becomes maximum for circular polarization. With the aid of a microscopic theory and a detailed analysis of the measured spectra, we reveal that such anomalous enhancement encodes the characteristic topology of the band structure that originates from the interplay of strong spin–orbit coupling and time-reversal symmetry protection. The implications are in ultrafast probing of topological phase transitions, light-field driven dissipationless electronics, and quantum computation.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Strong-field physics in three-dimensional topological insulators - Baykusheva, Denitsa Rangelova; Chacón, Alexis; Kim, Dasol; Kim, Dong Eon; Reis, David A.; Ghimire, Shambhu (Physical Review A)
We investigate theoretically the strong-field regime of light-matter interactions in the topological-insulator class of quantum materials. In particular, we focus on the process of nonperturbative high-order harmonic generation from the paradigmatic three-dimensional topological insulator bismuth selenide (Bi2Se3) subjected to intense midinfrared laser fields. We analyze the contributions from the spin-orbit-coupled bulk states and the topological surface bands separately and reveal a major difference in how their harmonic yields depend on the ellipticity of the laser field. Bulk harmonics show a monotonic decrease in their yield as the ellipticity increases, in a manner reminiscent of high harmonic generation in gaseous media. However, the surface contribution exhibits a highly nontrivial dependence, culminating with a maximum for circularly polarized fields. We attribute the observed anomalous behavior to (i) the enhanced amplitude and the circular pattern of the interband dipole and the Berry connections in the vicinity of the Dirac point and (ii) the influence of the higher-order, hexagonal warping terms in the Hamiltonian, which are responsible for the hexagonal deformation of the energy surface at higher momenta. The latter are associated directly with spin-orbit-coupling parameters. Our results thus establish the sensitivity of strong-field-driven high harmonic emission to the topology of the band structure as well as to the manifestations of spin-orbit interaction.

Attosecond interferometry of shape resonances in the recoil frame of CF4 - Heck, Saijoscha; Baykusheva, Denitsa Rangelova; Han, Meng; Ji, Jia-Bao; Perry, Conaill; Gong, Xiaochun; Wörner, Hans Jakob (Science Advances)
Shape resonances play a central role in many areas of science, but the real-time measurement of the associated many-body dynamics remains challenging. Here, we present measurements of recoil frame angle-resolved photoionization delays in the vicinity of shape resonances of CF4. This technique provides insights into the spatiotemporal photoionization dynamics of molecular shape resonances. We find delays of up to ∼600 as in the ionization out of the highest occupied molecular orbital (HOMO) with a strong dependence on the emission direction and a pronounced asymmetry along the dissociation axis. Comparison with quantum-scattering calculations traces the asymmetries to the interference of a small subset of partial waves at low kinetic energies and, additionally, to the interference of two overlapping shape resonances in the HOMO-1 channel. Our experimental and theoretical results establish a broadly applicable approach to space- and time-resolved photoionization dynamics in the molecular frame.
Keywords: Multidisciplinary

Science with the ultraviolet explorer (UVEX) - Kulkarni, S. R.; Harrison, Fiona A.; Grefenstette, Brian W.; Earnshaw, Hannah P.; Andreoni, Igor; Berg, Danielle A.; Bloom, Joshua S.; Cenko, S. Bradley; Chornock, Ryan; Christiansen, Jessie L.; Coughlin, Michael W.; Criswell, Alexander Wuollet; et al. (arXiv)
UVEX is a proposed medium class Explorer mission designed to provide crucial missing capabilities that will address objectives central to a broad range of modern astrophysics. The UVEX design has two co-aligned wide-field imagers operating in the FUV and NUV and a powerful broadband medium resolution spectrometer. In its two-year baseline mission, UVEX will perform a multi-cadence synoptic all-sky survey 50/100 times deeper than GALEX in the NUV/FUV, cadenced surveys of the Large and Small Magellanic Clouds, rapid target of opportunity followup, as well as spectroscopic followup of samples of stars and galaxies. The science program is built around three pillars. First, UVEX will explore the low-mass, low-metallicity galaxy frontier through imaging and spectroscopic surveys that will probe key aspects of the evolution of galaxies by understanding how star formation and stellar evolution at low metallicities affect the growth and evolution of low-metallicity, low-mass galaxies in the local universe. Such galaxies contain half the mass in the local universe, and are analogs for the first galaxies, but observed at distances that make them accessible to detailed study. Second, UVEX will explore the dynamic universe through time-domain surveys and prompt spectroscopic followup capability will probe the environments, energetics, and emission processes in the early aftermaths of gravitational wave-discovered compact object mergers, discover hot, fast UV transients, and diagnose the early stages of stellar explosions. Finally, UVEX will become a key community resource by leaving a large all-sky legacy data set, enabling a wide range of scientific studies and filling a gap in the new generation of wide-field, sensitive optical and infrared surveys provided by the Rubin, Euclid, and Roman observatories. This paper discusses the scientific potential of UVEX, and the broad scientific program.

On nonlinear problems of parabolic type with implicit constitutive equations involving flux - Bulíček, Miroslav; Maringová, Erika; Málek, Josef (Mathematical Models and Methods in Applied Sciences)
We study systems of nonlinear partial differential equations of parabolic type, in which the elliptic operator is replaced by the first-order divergence operator acting on a flux function, which is related to the spatial gradient of the unknown through an additional implicit equation. This setting, broad enough in terms of applications, significantly expands the paradigm of nonlinear parabolic problems. Formulating four conditions concerning the form of the implicit equation, we first show that these conditions describe a maximal monotone p-coercive graph. We then establish the global-in-time and large-data existence of a (weak) solution and its uniqueness. To this end, we adopt and significantly generalize Minty’s method of monotone mappings. A unified theory, containing several novel tools, is developed in a way to be tractable from the point of view of numerical approximations.
Keywords: Nonlinear parabolic systems; implicit constitutive theory; weak solutions; existence; uniqueness

Brief announcement: Be prepared when network goes bad: An asynchronous view-change protocol - Gelashvili, Rati; Kokoris Kogias, Eleftherios; Spiegelman, Alexander; Xiang, Zhuolun (Proceedings of the 2021 ACM Symposium on Principles of Distributed Computing)
The popularity of permissioned blockchain systems demands BFT SMR protocols that are efficient under good network conditions (synchrony) and robust under bad network conditions (asynchrony). The state-of-the-art partially synchronous BFT SMR protocols provide optimal linear communication cost per decision under synchrony and good leaders, but lose liveness under asynchrony. On the other hand, the state-of-the-art asynchronous BFT SMR protocols are live even under asynchrony, but always pay quadratic cost even under synchrony. In this paper, we propose a BFT SMR protocol that achieves the best of both worlds -- optimal linear cost per decision under good networks and leaders, optimal quadratic cost per decision under bad networks, and remains always live.
Keywords: optimal; state machine replication; fallback; asynchrony; byzantine faults

Entanglement view of dynamical quantum phase transitions - De Nicola, Stefano; Michailidis, Alexios; Serbyn, Maksym (Physical Review Letters)
The analogy between an equilibrium partition function and the return probability in many-body unitary dynamics has led to the concept of dynamical quantum phase transition (DQPT). DQPTs are defined by nonanalyticities in the return amplitude and are present in many models. In some cases, DQPTs can be related to equilibrium concepts, such as order parameters, yet their universal description is an open question. In this Letter, we provide first steps toward a classification of DQPTs by using a matrix product state description of unitary dynamics in the thermodynamic limit. This allows us to distinguish the two limiting cases of “precession” and “entanglement” DQPTs, which are illustrated using an analytical description in the quantum Ising model. While precession DQPTs are characterized by a large entanglement gap and are semiclassical in their nature, entanglement DQPTs occur near avoided crossings in the entanglement spectrum and can be distinguished by a complex pattern of nonlocal correlations. We demonstrate the existence of precession and entanglement DQPTs beyond Ising models, discuss observables that can distinguish them, and relate their interplay to complex DQPT phenomenology.
Keywords: General Physics and Astronomy

mRNA surveillance complex PELOTA-HBS1 eegulates phosphoinositide-sependent protein kinase1 and plant growth - Kong, W; Tan, Shutang; Zhao, Q; Lin, DL; Xu, ZH; Friml, Jiří; Xue, HW (Plant Physiology)
The quality control system for messenger RNA (mRNA) is fundamental for cellular activities in eukaryotes. To elucidate the molecular mechanism of 3'-Phosphoinositide-Dependent Protein Kinase1 (PDK1), a master regulator that is essential throughout eukaryotic growth and development, we employed a forward genetic approach to screen for suppressors of the loss-of-function T-DNA insertion double mutant pdk1.1 pdk1.2 in Arabidopsis thaliana. Notably, the severe growth attenuation of pdk1.1 pdk1.2 was rescued by sop21 (suppressor of pdk1.1 pdk1.2), which harbours a loss-of-function mutation in PELOTA1 (PEL1). PEL1 is a homologue of mammalian PELOTA and yeast (Saccharomyces cerevisiae) DOM34p, which each form a heterodimeric complex with the GTPase HBS1 (HSP70 SUBFAMILY B SUPPRESSOR1, also called SUPERKILLER PROTEIN7, SKI7), a protein that is responsible for ribosomal rescue and thereby assures the quality and fidelity of mRNA molecules during translation. Genetic analysis further revealed that a dysfunctional PEL1-HBS1 complex failed to degrade the T-DNA-disrupted PDK1 transcripts, which were truncated but functional, and thus rescued the growth and developmental defects of pdk1.1 pdk1.2. Our studies demonstrated the functionality of a homologous PELOTA-HBS1 complex and identified its essential regulatory role in plants, providing insights into the mechanism of mRNA quality control.

Tight frames and related geometric problems - Ivanov, Grigory (Canadian Mathematical Bulletin)
A tight frame is the orthogonal projection of some orthonormal basis of Rn onto Rk. We show that a set of vectors is a tight frame if and only if the set of all cross products of these vectors is a tight frame. We reformulate a range of problems on the volume of projections (or sections) of regular polytopes in terms of tight frames and write a first-order necessary condition for local extrema of these problems. As applications, we prove new results for the problem of maximization of the volume of zonotopes.
Keywords: General Mathematics; Tight frame; Grassmannian; zonotope

AGC kinases and MAB4/MEL proteins maintain PIN polarity by limiting lateral diffusion in plant cells - Glanc, Matous; Van Gelderen, K; Hörmayer, Lukas; Tan, Shutang; Naramoto, S; Zhang, Xixi; Domjan, David; Vcelarova, L; Hauschild, Robert; Johnson, Alexander J; de Koning, E; van Dop, M; et al. (Current Biology)
Polar subcellular localization of the PIN exporters of the phytohormone auxin is a key determinant of directional, intercellular auxin transport and thus a central topic of both plant cell and developmental biology. Arabidopsis mutants lacking PID, a kinase that phosphorylates PINs, or the MAB4/MEL proteins of unknown molecular function display PIN polarity defects and phenocopy pin mutants, but mechanistic insights into how these factors convey PIN polarity are missing. Here, by combining protein biochemistry with quantitative live-cell imaging, we demonstrate that PINs, MAB4/MELs, and AGC kinases interact in the same complex at the plasma membrane. MAB4/MELs are recruited to the plasma membrane by the PINs and in concert with the AGC kinases maintain PIN polarity through limiting lateral diffusion-based escape of PINs from the polar domain. The PIN-MAB4/MEL-PID protein complex has self-reinforcing properties thanks to positive feedback between AGC kinase-mediated PIN phosphorylation and MAB4/MEL recruitment. We thus uncover the molecular mechanism by which AGC kinases and MAB4/MEL proteins regulate PIN localization and plant development.

Auxin-regulated reversible inhibition of TMK1 signaling by MAKR2 modulates the dynamics of root gravitropism - Marquès-Bueno, MM; Armengot, L; Noack, LC; Bareille, J; Rodriguez Solovey, Lesia; Platre, MP; Bayle, V; Liu, M; Opdenacker, D; Vanneste, S; Möller, BK; Nimchuk, ZL; et al. (Current Biology)
Plants are able to orient their growth according to gravity, which ultimately controls both shoot and root architecture.1 Gravitropism is a dynamic process whereby gravistimulation induces the asymmetric distribution of the plant hormone auxin, leading to asymmetric growth, organ bending, and subsequent reset of auxin distribution back to the original pre-gravistimulation situation.1, 2, 3 Differential auxin accumulation during the gravitropic response depends on the activity of polarly localized PIN-FORMED (PIN) auxin-efflux carriers.1, 2, 3, 4 In particular, the timing of this dynamic response is regulated by PIN2,5,6 but the underlying molecular mechanisms are poorly understood. Here, we show that MEMBRANE ASSOCIATED KINASE REGULATOR2 (MAKR2) controls the pace of the root gravitropic response. We found that MAKR2 is required for the PIN2 asymmetry during gravitropism by acting as a negative regulator of the cell-surface signaling mediated by the receptor-like kinase TRANSMEMBRANE KINASE1 (TMK1).2,7, 8, 9, 10 Furthermore, we show that the MAKR2 inhibitory effect on TMK1 signaling is antagonized by auxin itself, which triggers rapid MAKR2 membrane dissociation in a TMK1-dependent manner. Our findings suggest that the timing of the root gravitropic response is orchestrated by the reversible inhibition of the TMK1 signaling pathway at the cell surface.

In situ small-angle X-ray scattering reveals solution phase discharge of Li–O2 batteries with weakly solvating electrolytes - Prehal, Christian; Samojlov, Aleksej; Nachtnebel, Manfred; Lovicar, Ludek; Kriechbaum, Manfred; Amenitsch, Heinz; Freunberger, Stefan Alexander (Proceedings of the National Academy of Sciences)
Electrodepositing insulating lithium peroxide (Li2O2) is the key process during discharge of aprotic Li–O2 batteries and determines rate, capacity, and reversibility. Current understanding states that the partition between surface adsorbed and dissolved lithium superoxide governs whether Li2O2 grows as a conformal surface film or larger particles, leading to low or high capacities, respectively. However, better understanding governing factors for Li2O2 packing density and capacity requires structural sensitive in situ metrologies. Here, we establish in situ small- and wide-angle X-ray scattering (SAXS/WAXS) as a suitable method to record the Li2O2 phase evolution with atomic to submicrometer resolution during cycling a custom-built in situ Li–O2 cell. Combined with sophisticated data analysis, SAXS allows retrieving rich quantitative structural information from complex multiphase systems. Surprisingly, we find that features are absent that would point at a Li2O2 surface film formed via two consecutive electron transfers, even in poorly solvating electrolytes thought to be prototypical for surface growth. All scattering data can be modeled by stacks of thin Li2O2 platelets potentially forming large toroidal particles. Li2O2 solution growth is further justified by rotating ring-disk electrode measurements and electron microscopy. Higher discharge overpotentials lead to smaller Li2O2 particles, but there is no transition to an electronically passivating, conformal Li2O2 coating. Hence, mass transport of reactive species rather than electronic transport through a Li2O2 film limits the discharge capacity. Provided that species mobilities and carbon surface areas are high, this allows for high discharge capacities even in weakly solvating electrolytes. The currently accepted Li–O2 reaction mechanism ought to be reconsidered.
Keywords: small-angle X-ray scattering; oxygen reduction; disproportionation; Li-air battery

Investigation of electrochemical and chemical processes occurring at positive potentials in “Water-in-Salt” electrolytes - Maffre, Marion; Bouchal, Roza; Freunberger, Stefan Alexander; Lindahl, Niklas; Johansson, Patrik; Favier, Frédéric; Fontaine, Olivier; Bélanger, Daniel (Journal of The Electrochemical Society)
Lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) based water-in-salt electrolytes (WiSEs) has recently emerged as a new promising class of electrolytes, primarily owing to their wide electrochemical stability windows (~3–4 V), that by far exceed the thermodynamic stability window of water (1.23 V). Upon increasing the salt concentration towards superconcentration the onset of the oxygen evolution reaction (OER) shifts more significantly than the hydrogen evolution reaction (HER) does. The OER shift has been explained by the accumulation of hydrophobic anions blocking water access to the electrode surface, hence by double layer theory. Here we demonstrate that the processes during oxidation are much more complex, involving OER, carbon and salt decomposition by OER intermediates, and salt precipitation upon local oversaturation. The positive shift in the onset potential of oxidation currents was elucidated by combining several advanced analysis techniques: rotating ring-disk electrode voltammetry, online electrochemical mass spectrometry, and X-ray photoelectron spectroscopy, using both dilute and superconcentrated electrolytes. The results demonstrate the importance of reactive OER intermediates and surface films for electrolyte and electrode stability and motivate further studies of the nature of the electrode.
Keywords: Renewable Energy; Sustainability and the Environment; Electrochemistry; Materials Chemistry; Electronic; Optical and Magnetic Materials; Surfaces; Coatings and Films; Condensed Matter Physics

Dendritic cell actin dynamics control contact duration and priming efficiency at the immunological synapse - Leithner, Alexander F; Altenburger, LM; Hauschild, R; Assen, Frank P; Rottner, K; TEB, Stradal; Diz-Muñoz, A; Stein, JV; Sixt, Michael K (Journal of Cell Biology)
Dendritic cells (DCs) are crucial for the priming of naive T cells and the initiation of adaptive immunity. Priming is initiated at a heterologous cell–cell contact, the immunological synapse (IS). While it is established that F-actin dynamics regulates signaling at the T cell side of the contact, little is known about the cytoskeletal contribution on the DC side. Here, we show that the DC actin cytoskeleton is decisive for the formation of a multifocal synaptic structure, which correlates with T cell priming efficiency. DC actin at the IS appears in transient foci that are dynamized by the WAVE regulatory complex (WRC). The absence of the WRC in DCs leads to stabilized contacts with T cells, caused by an increase in ICAM1-integrin–mediated cell–cell adhesion. This results in lower numbers of activated and proliferating T cells, demonstrating an important role for DC actin in the regulation of immune synapse functionality.

The logic of developing neocortical circuits in health and disease - Hanganu-Opatz, Ileana L.; Butt, Simon J. B.; Hippenmeyer, Simon; De Marco García, Natalia V.; Cardin, Jessica A.; Voytek, Bradley; Muotri, Alysson R. (The Journal of Neuroscience)
The sensory and cognitive abilities of the mammalian neocortex are underpinned by intricate columnar and laminar circuits formed from an array of diverse neuronal populations. One approach to determining how interactions between these circuit components give rise to complex behavior is to investigate the rules by which cortical circuits are formed and acquire functionality during development. This review summarizes recent research on the development of the neocortex, from genetic determination in neural stem cells through to the dynamic role that specific neuronal populations play in the earliest circuits of neocortex, and how they contribute to emergent function and cognition. While many of these endeavors take advantage of model systems, consideration will also be given to advances in our understanding of activity in nascent human circuits. Such cross-species perspective is imperative when investigating the mechanisms underlying the dysfunction of early neocortical circuits in neurodevelopmental disorders, so that one can identify targets amenable to therapeutic intervention.
Keywords: General Neuroscience

Optimal combination of linear and spectral estimators for generalized linear models - Mondelli, Marco; Thrampoulidis, Christos; Venkataramanan, Ramji (Foundations of Computational Mathematics)
We study the problem of recovering an unknown signal 𝑥𝑥 given measurements obtained from a generalized linear model with a Gaussian sensing matrix. Two popular solutions are based on a linear estimator 𝑥𝑥^L and a spectral estimator 𝑥𝑥^s. The former is a data-dependent linear combination of the columns of the measurement matrix, and its analysis is quite simple. The latter is the principal eigenvector of a data-dependent matrix, and a recent line of work has studied its performance. In this paper, we show how to optimally combine 𝑥𝑥^L and 𝑥𝑥^s. At the heart of our analysis is the exact characterization of the empirical joint distribution of (𝑥𝑥,𝑥𝑥^L,𝑥𝑥^s) in the high-dimensional limit. This allows us to compute the Bayes-optimal combination of 𝑥𝑥^L and 𝑥𝑥^s, given the limiting distribution of the signal 𝑥𝑥. When the distribution of the signal is Gaussian, then the Bayes-optimal combination has the form 𝜃𝑥𝑥^L+𝑥𝑥^s and we derive the optimal combination coefficient. In order to establish the limiting distribution of (𝑥𝑥,𝑥𝑥^L,𝑥𝑥^s), we design and analyze an approximate message passing algorithm whose iterates give 𝑥𝑥^L and approach 𝑥𝑥^s. Numerical simulations demonstrate the improvement of the proposed combination with respect to the two methods considered separately.
Keywords: Applied Mathematics; Computational Theory and Mathematics; Computational Mathematics; Analysis

Triangulating submanifolds: An elementary and quantified version of Whitney’s method - Boissonnat, Jean-Daniel; Kachanovich, Siargey; Wintraecken, Mathijs (Discrete & Computational Geometry)
We quantise Whitney’s construction to prove the existence of a triangulation for any C^2 manifold, so that we get an algorithm with explicit bounds. We also give a new elementary proof, which is completely geometric.
Keywords: Theoretical Computer Science; Computational Theory and Mathematics; Geometry and Topology; Discrete Mathematics and Combinatorics

The BCS energy gap at low density - Lauritsen, Asbjørn Bækgaard (Letters in Mathematical Physics)
We show that the energy gap for the BCS gap equation is Ξ=μ(8e−2+o(1))exp(π2μ−−√a) in the low density limit μ→0. Together with the similar result for the critical temperature by Hainzl and Seiringer (Lett Math Phys 84: 99–107, 2008), this shows that, in the low density limit, the ratio of the energy gap and critical temperature is a universal constant independent of the interaction potential V. The results hold for a class of potentials with negative scattering length a and no bound states.
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

New inertial projection methods for solving multivalued variational inequality problems beyond monotonicity - Izuchukwu, Chinedu; Shehu, Yekini (Networks and Spatial Economics)
In this paper, we present two new inertial projection-type methods for solving multivalued variational inequality problems in finite-dimensional spaces. We establish the convergence of the sequence generated by these methods when the multivalued mapping associated with the problem is only required to be locally bounded without any monotonicity assumption. Furthermore, the inertial techniques that we employ in this paper are quite different from the ones used in most papers. Moreover, based on the weaker assumptions on the inertial factor in our methods, we derive several special cases of our methods. Finally, we present some experimental results to illustrate the profits that we gain by introducing the inertial extrapolation steps.
Keywords: Computer Networks and Communications; Software; Artificial Intelligence

Probabilistic convergence and stability of random mapper graphs - Brown, Adam; Bobrowski, Omer; Munch, Elizabeth; Wang, Bei (Journal of Applied and Computational Topology)
We study the probabilistic convergence between the mapper graph and the Reeb graph of a topological space X equipped with a continuous function f:X→R. We first give a categorification of the mapper graph and the Reeb graph by interpreting them in terms of cosheaves and stratified covers of the real line R. We then introduce a variant of the classic mapper graph of Singh et al. (in: Eurographics symposium on point-based graphics, 2007), referred to as the enhanced mapper graph, and demonstrate that such a construction approximates the Reeb graph of (X,f) when it is applied to points randomly sampled from a probability density function concentrated on (X,f). Our techniques are based on the interleaving distance of constructible cosheaves and topological estimation via kernel density estimates. Following Munch and Wang (In: 32nd international symposium on computational geometry, volume 51 of Leibniz international proceedings in informatics (LIPIcs), Dagstuhl, Germany, pp 53:1–53:16, 2016), we first show that the mapper graph of (X,f), a constructible R-space (with a fixed open cover), approximates the Reeb graph of the same space. We then construct an isomorphism between the mapper of (X,f) to the mapper of a super-level set of a probability density function concentrated on (X,f). Finally, building on the approach of Bobrowski et al. (Bernoulli 23(1):288–328, 2017b), we show that, with high probability, we can recover the mapper of the super-level set given a sufficiently large sample. Our work is the first to consider the mapper construction using the theory of cosheaves in a probabilistic setting. It is part of an ongoing effort to combine sheaf theory, probability, and statistics, to support topological data analysis with random data.

Polygenic local adaptation in metapopulations: A stochastic eco‐evolutionary model - Szep, Eniko; Sachdeva, Himani; Barton, Nicholas H (Evolution)
This paper analyses the conditions for local adaptation in a metapopulation with infinitely many islands under a model of hard selection, where population size depends on local fitness. Each island belongs to one of two distinct ecological niches or habitats. Fitness is influenced by an additive trait which is under habitat‐dependent directional selection. Our analysis is based on the diffusion approximation and accounts for both genetic drift and demographic stochasticity. By neglecting linkage disequilibria, it yields the joint distribution of allele frequencies and population size on each island. We find that under hard selection, the conditions for local adaptation in a rare habitat are more restrictive for more polygenic traits: even moderate migration load per locus at very many loci is sufficient for population sizes to decline. This further reduces the efficacy of selection at individual loci due to increased drift and because smaller populations are more prone to swamping due to migration, causing a positive feedback between increasing maladaptation and declining population sizes. Our analysis also highlights the importance of demographic stochasticity, which exacerbates the decline in numbers of maladapted populations, leading to population collapse in the rare habitat at significantly lower migration than predicted by deterministic arguments.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics; General Agricultural and Biological Sciences

Homage to Felsenstein 1981, or why are there so few/many species? - Butlin, Roger K.; Servedio, Maria R.; Smadja, Carole M.; Bank, Claudia; Barton, Nicholas H; Flaxman, Samuel M.; Giraud, Tatiana; Hopkins, Robin; Larson, Erica L.; Maan, Martine E.; Meier, Joana; Merrill, Richard; et al. (Evolution)
If there are no constraints on the process of speciation, then the number of species might be expected to match the number of available niches and this number might be indefinitely large. One possible constraint is the opportunity for allopatric divergence. In 1981, Felsenstein used a simple and elegant model to ask if there might also be genetic constraints. He showed that progress towards speciation could be described by the build‐up of linkage disequilibrium among divergently selected loci and between these loci and those contributing to other forms of reproductive isolation. Therefore, speciation is opposed by recombination, because it tends to break down linkage disequilibria. Felsenstein then introduced a crucial distinction between “two‐allele” models, which are subject to this effect, and “one‐allele” models, which are free from the recombination constraint. These fundamentally important insights have been the foundation for both empirical and theoretical studies of speciation ever since.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics; General Agricultural and Biological Sciences

Supplementary code for: Polygenic local adaptation in metapopulations: A stochastic eco-evolutionary model - Szep, Eniko; Sachdeva, Himani; Barton, Nicholas H
This paper analyzes the conditions for local adaptation in a metapopulation with infinitely many islands under a model of hard selection, where population size depends on local fitness. Each island belongs to one of two distinct ecological niches or habitats. Fitness is influenced by an additive trait which is under habitat-dependent directional selection. Our analysis is based on the diffusion approximation and accounts for both genetic drift and demographic stochasticity. By neglecting linkage disequilibria, it yields the joint distribution of allele frequencies and population size on each island. We find that under hard selection, the conditions for local adaptation in a rare habitat are more restrictive for more polygenic traits: even moderate migration load per locus at very many loci is sufficient for population sizes to decline. This further reduces the efficacy of selection at individual loci due to increased drift and because smaller populations are more prone to swamping due to migration, causing a positive feedback between increasing maladaptation and declining population sizes. Our analysis also highlights the importance of demographic stochasticity, which exacerbates the decline in numbers of maladapted populations, leading to population collapse in the rare habitat at significantly lower migration than predicted by deterministic arguments.

Using replicate hybrid zones to understand the genomic basis of adaptive divergence - Westram, Anja M; Faria, Rui; Johannesson, Kerstin; Butlin, Roger (Molecular Ecology)
Combining hybrid zone analysis with genomic data is a promising approach to understanding the genomic basis of adaptive divergence. It allows for the identification of genomic regions underlying barriers to gene flow. It also provides insights into spatial patterns of allele frequency change, informing about the interplay between environmental factors, dispersal and selection. However, when only a single hybrid zone is analysed, it is difficult to separate patterns generated by selection from those resulting from chance. Therefore, it is beneficial to look for repeatable patterns across replicate hybrid zones in the same system. We applied this approach to the marine snail Littorina saxatilis, which contains two ecotypes, adapted to wave-exposed rocks vs. high-predation boulder fields. The existence of numerous hybrid zones between ecotypes offered the opportunity to test for the repeatability of genomic architectures and spatial patterns of divergence. We sampled and phenotyped snails from seven replicate hybrid zones on the Swedish west coast and genotyped them for thousands of single nucleotide polymorphisms. Shell shape and size showed parallel clines across all zones. Many genomic regions showing steep clines and/or high differentiation were shared among hybrid zones, consistent with a common evolutionary history and extensive gene flow between zones, and supporting the importance of these regions for divergence. In particular, we found that several large putative inversions contribute to divergence in all locations. Additionally, we found evidence for consistent displacement of clines from the boulder–rock transition. Our results demonstrate patterns of spatial variation that would not be accessible without continuous spatial sampling, a large genomic data set and replicate hybrid zones.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics

Seedling developmental defects upon blocking CINNAMATE-4-HYDROXYLASE are caused by perturbations in auxin transport - El Houari, I; Van Beirs, C; Arents, HE; Han, Huibin; Chanoca, A; Opdenacker, D; Pollier, J; Storme, V; Steenackers, W; Quareshy, M; Napier, R; Beeckman, T; et al. (New Phytologist)
• The phenylpropanoid pathway serves a central role in plant metabolism, providing numerous compounds involved in diverse physiological processes. Most carbon entering the pathway is incorporated into lignin. Although several phenylpropanoid pathway mutants show seedling growth arrest, the role for lignin in seedling growth and development is unexplored. • We use complementary pharmacological and genetic approaches to block CINNAMATE‐4‐HYDROXYLASE (C4H) functionality in Arabidopsis seedlings and a set of molecular and biochemical techniques to investigate the underlying phenotypes. • Blocking C4H resulted in reduced lateral rooting and increased adventitious rooting apically in the hypocotyl. These phenotypes coincided with an inhibition in auxin transport. The upstream accumulation in cis‐cinnamic acid was found to likely cause polar auxin transport inhibition. Conversely, a downstream depletion in lignin perturbed phloem‐mediated auxin transport. Restoring lignin deposition effectively reestablished phloem transport and, accordingly, auxin homeostasis. • Our results show that the accumulation of bioactive intermediates and depletion in lignin jointly cause the aberrant phenotypes upon blocking C4H, and demonstrate that proper deposition of lignin is essential for the establishment of auxin distribution in seedlings. Our data position the phenylpropanoid pathway and lignin in a new physiological framework, consolidating their importance in plant growth and development.

PIPE‐cloned human IgE and IgG4 antibodies: New tools for investigating cow's milk allergy and tolerance - Pranger, Christina L.; Fazekas-Singer, Judit; Köhler, Verena K.; Pali‐Schöll, Isabella; Fiocchi, Alessandro; Karagiannis, Sophia N.; Zenarruzabeitia, Olatz; Borrego, Francisco; Jensen‐Jarolim, Erika (Allergy)
Keywords: Immunology; Immunology and Allergy

Salicylic acid regulates PIN2 auxin transporter hyper-clustering and root gravitropic growth via Remorin-dependent lipid nanodomain organization in Arabidopsis thaliana - Ke, M; Ma, Z; Wang, D; Sun, Y; Wen, C; Huang, D; Chen, Z; Yang, L; Tan, Shutang; Li, R; Friml, Jiří; Miao, Y; et al. (New Phytologist)
To adapt to the diverse array of biotic and abiotic cues, plants have evolved sophisticated mechanisms to sense changes in environmental conditions and modulate their growth. Growth-promoting hormones and defence signalling fine tune plant development antagonistically. During host-pathogen interactions, this defence-growth trade-off is mediated by the counteractive effects of the defence hormone salicylic acid (SA) and the growth hormone auxin. Here we revealed an underlying mechanism of SA regulating auxin signalling by constraining the plasma membrane dynamics of PIN2 auxin efflux transporter in Arabidopsis thaliana roots. The lateral diffusion of PIN2 proteins is constrained by SA signalling, during which PIN2 proteins are condensed into hyperclusters depending on REM1.2-mediated nanodomain compartmentalisation. Furthermore, membrane nanodomain compartmentalisation by SA or Remorin (REM) assembly significantly suppressed clathrin-mediated endocytosis. Consequently, SA-induced heterogeneous surface condensation disrupted asymmetric auxin distribution and the resultant gravitropic response. Our results demonstrated a defence-growth trade-off mechanism by which SA signalling crosstalked with auxin transport by concentrating membrane-resident PIN2 into heterogeneous compartments.

Bosonic collective excitations in Fermi gases - Benedikter, Niels P (Reviews in Mathematical Physics)
Hartree–Fock theory has been justified as a mean-field approximation for fermionic systems. However, it suffers from some defects in predicting physical properties, making necessary a theory of quantum correlations. Recently, bosonization of many-body correlations has been rigorously justified as an upper bound on the correlation energy at high density with weak interactions. We review the bosonic approximation, deriving an effective Hamiltonian. We then show that for systems with Coulomb interaction this effective theory predicts collective excitations (plasmons) in accordance with the random phase approximation of Bohm and Pines, and with experimental observation.

The polaron at strong coupling - Seiringer, Robert (Reviews in Mathematical Physics)
We review old and new results on the Fröhlich polaron model. The discussion includes the validity of the (classical) Pekar approximation in the strong coupling limit, quantum corrections to this limit, as well as the divergence of the effective polaron mass.
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

Multi-cover persistence and Delaunay mosaics - Osang, Georg F
In this thesis we study persistence of multi-covers of Euclidean balls and the geometric structures underlying their computation, in particular Delaunay mosaics and Voronoi tessellations. The k-fold cover for some discrete input point set consists of the space where at least k balls of radius r around the input points overlap. Persistence is a notion that captures, in some sense, the topology of the shape underlying the input. While persistence is usually computed for the union of balls, the k-fold cover is of interest as it captures local density, and thus might approximate the shape of the input better if the input data is noisy. To compute persistence of these k-fold covers, we need a discretization that is provided by higher-order Delaunay mosaics. We present and implement a simple and efficient algorithm for the computation of higher-order Delaunay mosaics, and use it to give experimental results for their combinatorial properties. The algorithm makes use of a new geometric structure, the rhomboid tiling. It contains the higher-order Delaunay mosaics as slices, and by introducing a filtration function on the tiling, we also obtain higher-order α-shapes as slices. These allow us to compute persistence of the multi-covers for varying radius r; the computation for varying k is less straight-foward and involves the rhomboid tiling directly. We apply our algorithms to experimental sphere packings to shed light on their structural properties. Finally, inspired by periodic structures in packings and materials, we propose and implement an algorithm for periodic Delaunay triangulations to be integrated into the Computational Geometry Algorithms Library (CGAL), and discuss the implications on persistence for periodic data sets.

Fluctuations in the spectrum of random matrices - Cipolloni, Giorgio
In the first part of the thesis we consider Hermitian random matrices. Firstly, we consider sample covariance matrices XX∗ with X having independent identically distributed (i.i.d.) centred entries. We prove a Central Limit Theorem for differences of linear statistics of XX∗ and its minor after removing the first column of X. Secondly, we consider Wigner-type matrices and prove that the eigenvalue statistics near cusp singularities of the limiting density of states are universal and that they form a Pearcey process. Since the limiting eigenvalue distribution admits only square root (edge) and cubic root (cusp) singularities, this concludes the third and last remaining case of the Wigner-Dyson-Mehta universality conjecture. The main technical ingredients are an optimal local law at the cusp, and the proof of the fast relaxation to equilibrium of the Dyson Brownian motion in the cusp regime. In the second part we consider non-Hermitian matrices X with centred i.i.d. entries. We normalise the entries of X to have variance N −1. It is well known that the empirical eigenvalue density converges to the uniform distribution on the unit disk (circular law). In the first project, we prove universality of the local eigenvalue statistics close to the edge of the spectrum. This is the non-Hermitian analogue of the TracyWidom universality at the Hermitian edge. Technically we analyse the evolution of the spectral distribution of X along the Ornstein-Uhlenbeck flow for very long time (up to t = +∞). In the second project, we consider linear statistics of eigenvalues for macroscopic test functions f in the Sobolev space H2+ϵ and prove their convergence to the projection of the Gaussian Free Field on the unit disk. We prove this result for non-Hermitian matrices with real or complex entries. The main technical ingredients are: (i) local law for products of two resolvents at different spectral parameters, (ii) analysis of correlated Dyson Brownian motions. In the third and final part we discuss the mathematically rigorous application of supersymmetric techniques (SUSY ) to give a lower tail estimate of the lowest singular value of X − z, with z ∈ C. More precisely, we use superbosonisation formula to give an integral representation of the resolvent of (X − z)(X − z)∗ which reduces to two and three contour integrals in the complex and real case, respectively. The rigorous analysis of these integrals is quite challenging since simple saddle point analysis cannot be applied (the main contribution comes from a non-trivial manifold). Our result improves classical smoothing inequalities in the regime |z| ≈ 1; this result is essential to prove edge universality for i.i.d. non-Hermitian matrices.

The inductive bias of ReLU networks on orthogonally separable data - Bui Thi Mai, Phuong; Lampert, Christoph (9th International Conference on Learning Representations)
We study the inductive bias of two-layer ReLU networks trained by gradient flow. We identify a class of easy-to-learn (`orthogonally separable') datasets, and characterise the solution that ReLU networks trained on such datasets converge to. Irrespective of network width, the solution turns out to be a combination of two max-margin classifiers: one corresponding to the positive data subset and one corresponding to the negative data subset. The proof is based on the recently introduced concept of extremal sectors, for which we prove a number of properties in the context of orthogonal separability. In particular, we prove stationarity of activation patterns from some time onwards, which enables a reduction of the ReLU network to an ensemble of linear subnetworks.

Persistence of the spectral gap for the Landau–Pekar equations - Feliciangeli, Dario; Rademacher, Simone Anna Elvira; Seiringer, Robert (Letters in Mathematical Physics)
The Landau–Pekar equations describe the dynamics of a strongly coupled polaron. Here, we provide a class of initial data for which the associated effective Hamiltonian has a uniform spectral gap for all times. For such initial data, this allows us to extend the results on the adiabatic theorem for the Landau–Pekar equations and their derivation from the Fröhlich model obtained in previous works to larger times.

The strongly coupled polaron on the torus: Quantum corrections to the Pekar asymptotics - Feliciangeli, Dario; Seiringer, Robert (arXiv)
We investigate the Fröhlich polaron model on a three-dimensional torus, and give a proof of the second-order quantum corrections to its ground-state energy in the strong-coupling limit. Compared to previous work in the confined case, the translational symmetry (and its breaking in the Pekar approximation) makes the analysis substantially more challenging.

Stateless model checking under a reads-value-from equivalence - Agarwal, Pratyush; Chatterjee, Krishnendu; Pathak, Shreya; Pavlogiannis, Andreas; Toman, Viktor (33rd International Conference on Computer-Aided Verification)
Stateless model checking (SMC) is one of the standard approaches to the verification of concurrent programs. As scheduling non-determinism creates exponentially large spaces of thread interleavings, SMC attempts to partition this space into equivalence classes and explore only a few representatives from each class. The efficiency of this approach depends on two factors: (a) the coarseness of the partitioning, and (b) the time to generate representatives in each class. For this reason, the search for coarse partitionings that are efficiently explorable is an active research challenge. In this work we present RVF-SMC , a new SMC algorithm that uses a novel reads-value-from (RVF) partitioning. Intuitively, two interleavings are deemed equivalent if they agree on the value obtained in each read event, and read events induce consistent causal orderings between them. The RVF partitioning is provably coarser than recent approaches based on Mazurkiewicz and “reads-from” partitionings. Our experimental evaluation reveals that RVF is quite often a very effective equivalence, as the underlying partitioning is exponentially coarser than other approaches. Moreover, RVF-SMC generates representatives very efficiently, as the reduction in the partitioning is often met with significant speed-ups in the model checking task.

Curvature driven interface evolution: Uniqueness properties of weak solution concepts - Hensel, Sebastian
The present thesis is concerned with the derivation of weak-strong uniqueness principles for curvature driven interface evolution problems not satisfying a comparison principle. The specific examples being treated are two-phase Navier-Stokes flow with surface tension, modeling the evolution of two incompressible, viscous and immiscible fluids separated by a sharp interface, and multiphase mean curvature flow, which serves as an idealized model for the motion of grain boundaries in an annealing polycrystalline material. Our main results - obtained in joint works with Julian Fischer, Tim Laux and Theresa M. Simon - state that prior to the formation of geometric singularities due to topology changes, the weak solution concept of Abels (Interfaces Free Bound. 9, 2007) to two-phase Navier-Stokes flow with surface tension and the weak solution concept of Laux and Otto (Calc. Var. Partial Differential Equations 55, 2016) to multiphase mean curvature flow (for networks in R^2 or double bubbles in R^3) represents the unique solution to these interface evolution problems within the class of classical solutions, respectively. To the best of the author's knowledge, for interface evolution problems not admitting a geometric comparison principle the derivation of a weak-strong uniqueness principle represented an open problem, so that the works contained in the present thesis constitute the first positive results in this direction. The key ingredient of our approach consists of the introduction of a novel concept of relative entropies for a class of curvature driven interface evolution problems, for which the associated energy contains an interfacial contribution being proportional to the surface area of the evolving (network of) interface(s). The interfacial part of the relative entropy gives sufficient control on the interface error between a weak and a classical solution, and its time evolution can be computed, at least in principle, for any energy dissipating weak solution concept. A resulting stability estimate for the relative entropy essentially entails the above mentioned weak-strong uniqueness principles. The present thesis contains a detailed introduction to our relative entropy approach, which in particular highlights potential applications to other problems in curvature driven interface evolution not treated in this thesis.

The reads-from equivalence for the TSO and PSO memory models - Bui, Truc Lam; Chatterjee, Krishnendu; Gautam, Tushar; Pavlogiannis, Andreas; Toman, Viktor (Proceedings of the ACM on Programming Languages)
In this work we solve the algorithmic problem of consistency verification for the TSO and PSO memory models given a reads-from map, denoted VTSO-rf and VPSO-rf, respectively. For an execution of n events over k threads and d variables, we establish novel bounds that scale as nk+1 for TSO and as nk+1· min(nk2, 2k· d) for PSO. Moreover, based on our solution to these problems, we develop an SMC algorithm under TSO and PSO that uses the RF equivalence. The algorithm is exploration-optimal, in the sense that it is guaranteed to explore each class of the RF partitioning exactly once, and spends polynomial time per class when k is bounded. Finally, we implement all our algorithms in the SMC tool Nidhugg, and perform a large number of experiments over benchmarks from existing literature. Our experimental results show that our algorithms for VTSO-rf and VPSO-rf provide significant scalability improvements over standard alternatives. Moreover, when used for SMC, the RF partitioning is often much coarser than the standard Shasha-Snir partitioning for TSO/PSO, which yields a significant speedup in the model checking task.
Keywords: safety; risk; reliability and quality; software